Metal–organic framework sensors for sustainable agriculture and environmental monitoring: Engineering, mechanisms, and future perspectives - Irfan Haidri; Muhammad Qasim; Qudrat Ullah; Muhammad Ali Amir; Waqas Haider; Hien Huu Nguyen; Athakorn Promwee (Environmental Nanotechnology, Monitoring & Management, 2026)

Spatial distribution and compartmental storage of microplastic particles in a tropical lowland river system (Perak river, Malaysia) - Sarva Mangala Praveena; Muhammad Nifail Sharif; Alif Ilhami Mohd Zamri; Mohd Amir Md Khalid; Mohd Firdaus Mohd Anuar; Vita Pramaningsih; Samuel Abiodun Kehinde (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Evolution of Maastrichtian paleoproductivity along the southern Tethys margin (Jordan): From upwelling to runoff - Maria Ardila-Sanchez; Jihede Haj Messaoud; Amir Kalifi; Khalil Ibrahim; Muhammad Usman; Israa S. Abu-Mahfouz; Samer Aljurf; Volker Vahrenkamp; John H. Powell; Frans van Buchem (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Adsorption-desorption nexus of biowaste-derived biochars towards potentially toxic elements: Unveiling challenges and paving paths for the large-scale mining and industrial soil applications - Javed Nawab; Ruby; Amir Hamza; Muhammad Waqas; Cosimo Magazzino; Matthias Kleinke; Irfan Ullah (Biomass and Bioenergy, 2026)

WheatSim: A process-based wheat model linking organ development, plant architecture, and field-scale responses under environmental variability - Zhuangji Wang; Dennis Timlin; Xiaocui Wu; Elnaz Ebrahimi; Bin Peng; Kirsten Paff; Christine Chang; Eunjin Han; Lisa Fultz; Amir Sadeghpour; Ezekiel Ahn; David Fleisher; et al. (Computers and Electronics in Agriculture, 2026)

Bioadaptive metal–organic frameworks in sustainable agriculture: Integrated crop protection, nutrient delivery, and beneficial microbial protection - Irfan Haidri; Muhammad Qasim; Qudrat Ullah; Ebadet Ali; Muhammad Ali Amir; Waqas Haider; Athakorn Promwee (Physiological and Molecular Plant Pathology, 2026)

Defect-engineered MIL-100(Fe) via acid modulation for enhanced adsorption and selectivity in dye removal from wastewater - Mohd Amir Asyraf Mohd Hamzah; Muhammad Ahnaf Mohd Azmi; Rickson Jun Jay Chia; Norhaniza Yusof; Woei Jye Lau; Ahmad Fauzi Ismail; Hasrinah Hasbullah (Journal of Water Process Engineering, 2026)

Rice husk-derived nanosilica alleviates aluminum accumulation and toxicity in Brassica napus by regulating cellular metabolism and antioxidant defense - Raheel Munir; Nazia Jan; Bahar Ali; Rana Muhammad Amir Gulzar; Muhammad Haseeb Javaid; Iqbal Hussain; Yinbo Gan (Environmental Research, 2026)

Corrigendum to “A review on biohydrogen production through dark fermentation via the lactate pathway” [Bioresour. Technol. 454 (2026) 134726] - Amir Izzuddin Adnan; Hassan Mohamed; Eqwan Roslan; Nur Atiqah Mohamad Aziz; Mouad Firah; Mohd Nur Ikhmal Salehmin; Bidattul Syirat Zainal; Muhammad Fikri Zulkornain; Farah Nurhikmah; Saifuddin Nomanbhay; Peer Mohamed Abdul; Sumaiya Zainal Abidin (Bioresource Technology, 2026)

Correction to: Magnetic Bentonite for Efficient Phosphate Removal from Wastewater: A Sustainable Strategy to Combat Eutrophication - Khizar Hussain Shah; Muhammad Imtiaz Rashid; Javairia Zubair; Saba Zafar; Abdul Amir; Akhtar Iqbal; Khurram Shahzad; Arshid Mahmood Ali (Water, Air, & Soil Pollution, 2026)

Self-powered electrochemical glucose sensing enabled by zirconium holmium oxide/MXene/graphene nanocomposites with integrated energy storage - Nora Mobark Farhan; Saba Khalil; M.S. Al-Buriahi; Muhammad Ali Hamza Shahbaz; Nissren Tamam; Amir Muhammad Afzal; Abhinav Kumar; Sohail Mumtaz (Analytica Chimica Acta, 2026)

Factors associated with mortality and recurrence among patients with multidrug-resistant tuberculosis (MDR-TB): a systematic review, meta-analysis and meta-regression - Lutfian Lutfian; Sidik Maulana; Jonathan Hasian Haposan; Izdihar Javier Wardika; Muhammad Amir Mukminin; Ibnu Syarifudin Hidayat; Sakinah Hilya Abida; Artha Maressa Theodora; Ayu Cetiya Mahayekti; Muhamad Zulfatul A’la; Ahmad Syauqy Tafrihani; Dikki Saputra; et al. (Infectious Diseases, 2026)

A review on biohydrogen production through dark fermentation via the lactate pathway - Amir Izzuddin Adnan; Hassan Mohamed; Eqwan Roslan; Nur Atiqah Mohamad Aziz; Mouad Firah; Mohd Nur Ikhmal Salehmin; Bidattul Syirat Zainal; Muhammad Fikri Zulkornain; Farah Nurhikmah; Saifuddin Nomanbhay; Peer Mohamed Abdul; Sumaiya Zainal Abidin (Bioresource Technology, 2026)

Characterization and Wound-Healing Effects of Fucoidan from Sargassum polycystum Collected in South Sulawesi in a Staphylococcus aureus-Infected Rat Model - Fausyiah Sasmitha AB; Frederika Tangdilintin; Sulistiawati Sulistiawati; Siti Nur Fatimah; Stephanie Stephanie; Muhammad Nur Amir; Syamsiah Syamsiah; Ngoc Dan Thuy Nguyen; Taifo Mahmud; Muhammad Nasrum Massi; Marianti Manggau (Marine Biotechnology, 2026)

Edaravone dexborneol in acute ischemic stroke: a systematic review and meta-analysis of randomized trials with clinical and thrombectomy-specific subgroup analyses - Eman Tariq; Hooriya Ahmed; Tayyaba Ikram Qazi; Abdul Muhaimin; Aleena Amir Malik; Javeria Soomro; Rahimeen Qureshi; Zainab Murtaza; Sarum Ali Khan; Wajeeha Komal; Hadia Tanveer; Rida Ameer; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Can baxdrostat redefine blood pressure control in resistant and uncontrolled hypertension? a systematic review, meta-analysis, and trial sequential analysis - Bilal Wazir Khan; Muhammad Yahya; Hamza Wazir Khan; Miguel Alejandro Rivas Perez; Tayyaba Ikram Qazi; Humaira Obaid; Muhammad Mustafa Khan; Muhammad Maaz Amjad; Muhammad Faaz Khan; Aneeq Mahmood Khan; Muhammad Junaid Khan; Sajjad Khan; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

The first record of the arboreal land snail Amphidromus leucoxanthus (Martens, 1864) from Peninsular Malaysia (Stylommatophora: Camaenidae) - Mohamad Afiq Aiman Asrin; Khairul Amar Zikrie Zainudin; Muhammad Amir Iqhwan Mohd Khaderi; Nur Muhammad Hazami Abdul Rahman; Faathrio Hudaya Zulfin; Mohammad Effendi Marzuki; Aainaa Amir; Kamarul Hambali (Molluscan Research, 2026)

Diosgenin-loaded niosomes ameliorate cadmium-induced neurotoxicity and endocrine disruption in female rats through modulation of oxidative stress, apoptosis, and inflammatory markers - Kanza Hashmi; Ammara Saleem; Shakila Sabir; Shahana Ehsan; Aisha Mobashar; Muhammad Imran khan; Shahnaz; Zulcaif Ahmad; Muhammad Furqan Akhtar; Musaab Dauelbait; Amir Bouallegue; Esmael M. Alyami; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Evolution and Biogeography of the Genus Heteropoda (Heteropodinae: Sparassidae) Across Southeast Asia - Shakal Khan Korai; Amir Khan Korai; Shengnan Li; Kamil Kabir; Kamran Haider; Muhammad Raheel Tariq; Arif Ali; Xiaoshan Wang (Zoologica Scripta, 2026)
Heteropoda huntsman spiders are large, fast‐moving predators widely distributed across tropical and subtropical regions, where they function as important nocturnal hunters. Despite their ecological prominence, the evolutionary and biogeographic history of the genus remains poorly resolved. Here, we analysed a six‐locus dataset (two mitochondrial and four nuclear genes) to estimate divergence times and reconstruct ancestral ranges within Heteropoda using Bayesian phylogenetic and statistical biogeographic approaches, and we assessed broad climatic suitability using genus‐level ecological niche modelling. Time‐calibrated analyses support the monophyly of Heteropoda and indicate that crown diversification began during the early Oligocene (~30 Ma; 95% HPD: 18–41 Ma). A primary split between Australasian and Asian lineages is inferred near the Oligocene–Miocene transition (~23 Ma; 95% HPD: 14–33 Ma), followed by radiation within Southeast and East Asia. Ancestral‐area reconstructions consistently recover Australasia as a key ancestral component and suggest repeated dispersal and isolation across the Sunda–Wallacea interface under conditions of long‐term tectonic instability. Ecological niche modelling identifies temperature, precipitation, and elevation as major correlates of climatic suitability, consistent with the predominance of Heteropoda in warm and humid environments. Together, these results provide an integrated temporal, spatial, and ecological framework for understanding diversification and present‐day distribution of Heteropoda across Southeast Asia and adjacent regions.

Exogenous brassinolide improves processing quality of cold-stored potato tubers by mitigating sweetening through integrated physiological and transcriptional regulation - Chao Wu; Xiaoting Fang; Lijun Liu; Qianyu Zhang; Xia Zhu; Muhammad Amir Shahzad; Juanjuan Liu; Kaiqin Zhang; Zhitong Ren; Shunlin Zheng (Food Chemistry, 2026)

Photocatalytic CO2 reduction: Fundamental principles, mechanistic pathways and material-specific kinetic insights - Syed Izaz Ali Shah; Muhammad Anwar; Wisal Ahmad; Muhammad Ateeq; Amir Zada; Noor S. Shah; Javed Ali Khan; Changseok Han (Chemical Engineering Journal, 2026)

Mapping of buried archaeological ruins using magnetic and gravity methods around the 17th-century fort of Gunong Biram, Aceh Besar, Indonesia - Amir Asyqari; Nazli Ismail; Muhammad Nanda; Tomi Afrizal; Muhammad Yanis; Deni Sutrisna; Repelita Wahyu Oetomo; Cut Dewi (Geosciences Journal, 2026)

Integrated modelling application for assessing impacts of climate and land use change on water balance in Hadejia river basin Northwestern Nigeria - Da’u Abba Umar; Mohammad Firuz Ramli; Amir Kamal Hamidon; Ruhil Amal Adnan; Shaharin Ibrahim; Muhammad Amar bin Zaudi; AbdulJalal AbdulSalam (Arabian Journal of Geosciences, 2026)

Structure-based virtual screening, molecular dynamics and MM-PBSA/GBSA analysis for the identification of novel CDK6 inhibitors against prostate cancer - Manzoor Ahmad; Muhammad Ajmal Khan; Ashraf Ullah Khan; Sadia Butt; Yahya Khan; Amir Zeb; Nadia Bibi; Aishma Khattak; Hina Ahsan; Ajaz Ahmad; Amin Ullah (In Silico Pharmacology, 2026)

Radiological contamination in soils near the world's largest rare earth minerals producing region and their impacts on human health: A summary analysis - Amir Hamza; Faisal Khan; Javed Nawab; Junaid Ghani; Sajid Ali; Yaseen Laghari; Luo Xin; Niaz Muhammad; Jing Cui; Zhenggui Wei (Journal of Environmental Radioactivity, 2026)

Protective potential of linalool against cyclophosphamide-induced interstitial cystitis: mechanistic insights from experimental and computational approaches - Irfan Anjum; Asfia Arooje; Saima; Fawad Naeem; Muhammad Naveed Mushtaq; Kashif Barkat; Zaka Ur Rehman; Syed Damin Abbas Hamdani; Shah Jahan; Mohammed Dauelbait; Amir Bouallegue; Esmael M. Alyami; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Green-synthesized nanoparticles used to restore soil health and reprogram plant resilience - Babar Iqbal; Inamullah; Amir Abdullah Khan; Ali Raza Khan; Rasheed Akbar; Muhammad Sohail Memon; Guanlin Li; Daolin Du (Journal of Environmental Chemical Engineering, 2026)

Individual and combined decontamination effect of aqueous ozone and plant extracts on fungi and aflatoxins in brown rice - Iqra Naeem; Amir Ismail; Yun Yun Gong; Muhammad Riaz; Muhammad Arif Shahzad; Aneela Hameed; Mubashir Aziz; Asif Mahmood; Waheed Al Masry; Muhammad Latif; Sher Ali; Carlos A.F. Oliveira (Food Control, 2026)

Remediation of Pb2+ Ions by Green Route Modified Carbon Nanotubes - Saba Zafar; Abdul Amir; Saira Arif; Fozia Bibi; Ammara Aftab; Muhammad Naeem Ahmed; Muhammad Waseem (Water, Air, & Soil Pollution, 2026)

Foliar Spraying with Plant Growth Regulators Mitigate Heat Stress in Late-Planted Potatoes: Enhancing Morpho-physiological Traits, Yield, and Quality - Chao Wu; Wensen Huang; Xiaoting Fang; Haiyan Ma; Wenwen Song; Kaiqin Zhang; Zhitong Ren; Muhammad Amir Shahzad; Juanjuan Liu; Cuiqin Yang; Shunlin Zheng (Potato Research, 2026)

Integrated physicomechanical, petrographic, and geochemical evaluation of eocene carbonate aggregates from the Salt Range, Pakistan - Khawaja Shoaib Ahmed; Muhammad Basharat; Amir Shahzad; Yasir Sirfraz; Muhammad Tayyib Riaz; Usama Shabir Abbasi; Salman Rasheed (Innovative Infrastructure Solutions, 2026)

Whole-genome characterization and functional–structural analysis of GST variants in Orang Asli with comparative insights from Malays - Aishah Farliani Shirat; Muhammad Yusuf Abdul Zaid; Nurul Azmir Amir Hashim; Nurul Huda Mohamad Ikbal; Mohd Nur Fakhruzzaman Noorizhab; Eng Keng Seow; Mohammad Masrin Md Zahrin; Thane Moze Darumalinggam; Muhammad Danish Badrul Hisham; Teh Lay Kek; Mohd Zaki Salleh (In Silico Pharmacology, 2026)

Agriculture, industry, and economic growth as determinants of carbon emissions in climate hotspots: evidence from dynamic causal analysis - Amir Mustafa; Naeem Ahmed; Munib Ahmed; Muhammad Adnan Bashir (Environment, Development and Sustainability, 2026)

Species-specific snag use and nesting ecology of cavity-nesting birds in managed plantations of Southern Punjab, Pakistan - Muhammad Talha Imtiaz; Ihsan Qadir; Kathryn E. Sieving; Ghulam Yasin; Syed Amir Manzoor; Muhammad Farooq Azhar; Muhammad Zubair (Environmental Monitoring and Assessment, 2026)

Hydraulic behavior of HAWT on a small scale with differences in the blade configuration by computational method - Dewi Puspita Sari; Imam Syofii; Kaprawi Sahim; Megawati Megawati; Muhammad Alhudari; Ahmad Fudholi; Amir Arifin; Gunawan Gunawan; Dendy Adanta; Kamaruzzaman Sopian (International Journal of Energy and Water Resources, 2026)

Retraction Note: Novel acetamide derivatives of 2-aminobenzimidazole prevent inflammatory arthritis in rats via suppression of pro-inflammatory mediators - Aymun Madni Zubair; Muhammad Nasir Hayat Malik; Waqas Younis; Muhammad Atif Hayat Malik; Shah Jahan; Ishtiaq Ahmed; Alamgeer Yuchi; Muhammad Naveed Mushtaq; Romeeza Tahir; Muhammad Bilal Sarwar; Muhammad Roman; Ayaz Ali Khan; et al. (Inflammopharmacology, 2026)

Ecological Niche Overlap and Environmental Associations Among Species of the Morchella (Morchellaceae, Pezizomycotina) From P.R. China - Akmal Muhammad; Yinglian Deng; Syed Amir Manzoor; Changlin (Charlie) Zhao (New Zealand Journal of Botany, 2026)
Morchella species, economically significant edible fungi, are affected by numerous environmental factors; however, details concerning their ecological niche are poorly understood. Consequently, this study aims to fill this deficiency by applying a modeling approach to the fundamental niche of the Morchella genus, incorporating species from the elata and esculenta clades. In this work, we examined the distribution patterns of Morchella species in relation to significant environmental factors. The MaxEnt algorithm was utilized to conclude habitat validity. The environmental variables incorporated into the final models comprised isothermality, temperature seasonality, maximum temperature of the warmest month, mean temperature of the warmest quarter, precipitation of the wettest month, precipitation seasonality, slope, and aspect. The PCA‐env analysis revealed that the first two axes accounted for 69.55% of the overall variation in climatic conditions across the ranges of the two clades (PC1 = 41.36% and PC2 = 28.19%). An analysis and comparison of the climatic space engaged by the two primary clades, along with their overlap, were conducted. These findings emphasized the utility of ecological niche modeling for understanding how climatic conditions can influence the dispersal of Morchella clades. These results aid in formulating enhanced conservation strategies and in informed decision‐making across different ecosystems. It is essential to adopt a holistic approach to ecological modeling to foster sustainable conservation, evaluate diversity, and manage the valuable Morchella resources.

Coprinellus gregariodiguttulatus , a New Coprinoid Species from Margalla Hills, Islamabad, Pakistan - Fahim Ullah; Malka Saba; Iram Fatima; Muhammad Asif; Mohsin Ullah; Fazli Maula; Wajahat Akram; Amir Sohail (New Zealand Journal of Botany, 2026)
Coprinellus gregariodiguttulatus is described as a new species from Quaid‐i‐Azam University, Islamabad, Pakistan, based on morphological and molecular analyses. The species is distinguished by its small gray to light gray basidiomata, paraboloid to hemispherical pileus, and oblong to obovoid or rarely lemon basidiospores. Phylogenetic analysis of the internal transcribed spacer (ITS) region supports its placement within Coprinellus sect. Disseminati is a distinct lineage, closely related to but separate from other known taxa. This discovery from an underexplored region highlights the potential for uncovering further novel fungal diversity in Pakistan.

Species-driven variability in soil health and carbon storage across bamboo plantations - Ghulam Yasin; Syed Amir Manzoor; Muhammad Farooq Azhar; Muhammad Talha Imtiaz; Shafeeq Ur Rahman; Islem Abid; Manal Abdulaziz Binobead; Rashid Iqbal (Environmental Monitoring and Assessment, 2026)

Anti-arthritic and anti-inflammatory effects of BMZD-2CPE in a CFA and carrageenan-induced animal model - Samiullah Wazir; Farah Abid; Aisha Mobashar; Arham Shabbir; Muhammad Awais; Humaira Nadeem; Hafiz Aamir Ali Kharl; Esmael M. Alyami; Amir Bouallegue; Norah Hamdi; Mohammed Bourhia; Abdullah R. Alanzi (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Geographic distribution patterns, population dynamics, and habitat vulnerability of endangered and endemic Trillium govanianum - Syed Waseem Gillani; Mushtaq Ahmad; Muhammad Manzoor; Muhammad Waheed; Raja Waqar Ahmed Khan; Amir Sohail (Environmental Monitoring and Assessment, 2026)

Structural, dielectric, and microstructural properties of Bi0.5(Na0.82K0.18)0.5Ti1–xNbxO3 ceramics: Effect of Nb doping on phase transition, grain growth, and electrical performance for dielectric, piezoelectric and energy storage applications - Salim Ullah; Zahid Ullah; Muhammad Amir Khan; Amir Ullah (Next Research, 2026)

Hermetic storage reduces postharvest losses in challenging ambient environments - Ehsan Khalid; Irfan Afzal; Muhammad Amir Bakhtavar (Journal of Stored Products Research, 2026)

Harvesting lithium from brines via high-selectivity nanofiltration integrated with membrane distillation - Amir Aghaei; Muhammad Amirul Islam; Vahid Rad; Aria Khalili; Afrouz Yousefi; Ahamd Arabi Shamsabadi; Masoud Soroush; Jae-Young Cho; Young-Hye La; Mohtada Sadrzadeh (Chemical Engineering Journal, 2026)

Magnetic Bentonite for Efficient Phosphate Removal from Wastewater: A Sustainable Strategy to Combat Eutrophication - Khizar Hussain Shah; Muhammad Imtiaz Rashid; Javairia Zubair; Saba Zafar; Abdul Amir; Akhtar Iqbal; Khurram Shahzad; Arshid Mahmood Ali (Water, Air, & Soil Pollution, 2026)

Ameliorating effect of veratric acid against mercury-induced neurologic deficit and reproductive toxicity in female rats - Saira Saeed; Qurat-Ul-Ain; Ammara Saleem; Muhammad Imran Khan; Kanwal Akhtar; Aslam Khan; Muhammad Furqan Akhtar; Amir Bouallegue; Mohammed Bourhia; Sultan F. Kadasah (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Enhancement of antioxidant and cytotoxicity by nanoliposome formulation of pentagamavunon-6 in breast cancer cells - Muhammad Nizam Zulfi Zakaria; A’liyatur Rosyidah; Diah Anggraini Wulandari; Ritmaleni Ritmaleni; Muhammad Novrizal Abdi Sahid; Muhaimin Rifa’i; Sjaikhurrizal El Muttaqien; Damai Ria Setyawati; Fransiska Christydira Sekaringtyas; Arbi Dimyati; Amir Hamzah; Riyona Desvy Pratiwi (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Neuroprotective Effects of Ficus deltoidea in Alzheimer’s Disease-Like Rat Model: Insights from Behavior, Histology, and Amyloid Pathology - Abdulhamid Sani Usman; Sushmitaa Dhevii Manoharan; Che Mohd Nasril Che Mohd Nassir; Hafizah Abdul Hamid; Zaw Myo Hein; Anwar Norazit; Jayakumar Murthy; Murizal Zainol; Mohd Amir Kamaruzzaman; Samaila Musa Chiroma; Muzaimi Mustapha; Mohamad Aris Mohd Moklas; et al. (Molecular Neurobiology, 2026)

Leapfrogging toward Sustainability: The role of renewable energy, energy imports, and debt on Pakistan's carbon emissions - Amir Imtiaz; Raj bahadur Singh Chandel; Muhammad Shahbaz; Zokir Mamadiyarov (Journal of Environmental Management, 2025)

Energy transition, globalization, and FDI: Pathways to achieve sustainable development goals in T-MEC countries - Hong Wu; Kashif Raza Abbasi; Muhammad Irfan; Stefania Pinzon; Amir Hamza (Gondwana Research, 2025)

Cutting edge advancements in biochar applications: thermochemical, fermentative, photocatalytic and electrocatalytic hydrogen production and storage - Muhammad Rizwan; M.H. Eisa; Amir Zada; Shohreh Azizi; Ahmed M. Alkaoud; Miqad S. Albishi; Hong Chen (Fuel, 2025)

The potential influence of food additives and contaminants on the gut microbiota: A comprehensive review - Sana Ullah; Sher Ali; Muhammad Atif; Muhib Ullah; Ghulam Nabi; Lucas Gabriel Dionisio Freire; Eliana Setsuko Kamimura; Amir Sasan Mozaffari Nejad; Carlos Augusto Fernandes de Oliveira (Food and Chemical Toxicology, 2025)

Polyamide thin film nanocomposite membranes modified with cationic nanogel for efficient Li+/Mg2+ separation - Elham Jashni; Amir Aghaei; Muhammad Amirul Islam; Amirhossein Taghipour; Forough Rezaie; Aria Khalili; Jae-Young Cho; Mohtada Sadrzadeh (Desalination, 2025)

Hydrographic Responses to Indian Ocean Dipole Events in a Semi-Enclosed Tropical Bay: a Case Study from Lampung Bay, Indonesia - Amir Yarkhasy Yuliardi; Gandhi Napitupulu; Septy Heltria; Muhammad Hafidz Ibnu Khaldun; Muhamad Gilang Arindra Putra; Delilla Suhanda (Thalassas: An International Journal of Marine Sciences, 2025)

Genomic insights into autosomal recessive epilepsy: novel pathogenic variants in ITPA and CLN5 identified in consanguineous families - Anees Muhammad; Fawad Inayat; Bilal Ahmad Sethi; Muhammad Kashif; Assad Ullah Khan; Shahzad Ahmad; Amir Atlas; Shoaib Ur Rehman; Muhammad Tahir Sarwar (Molecular Biology Reports, 2025)

Carbon Nanotubes Improve Quantitative and Qualitative Attributes of Potato (Solanum tuberosum L) Genotypes - Muhammad Ismail; Muhammad Imtiaz; Raham Sher Khan; Fazal Jalal; Fazal Said; Muhammad Ali Khan; Syed Hussain; Badshah Islam; Salman Khan; Sabir Khan; Atta Ullah; Maqsood Khan; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Morpho-palynological evaluation of family Poaceae from arid and semi-arid regions of Pakistan - Bibi Sadia; Mushtaq Ahmad; Wajia Noor; Syed Waseem Gillani; Muhammad Manzoor; Zhiduan Chen; Lixin Zhang; Shazia Sultana; Amir Sohail (Genetic Resources and Crop Evolution, 2025)

Using taxonomic tools to investigate palynological record of fossil plants from Pakistan - Shabir Ahmad; Mushtaq Ahmad; Rozina; Ateef Ullah; Hussain Shah; Amir Shahzad; Muhammad Abdullah; Khushdil Khan; Shadab Khan; Rashid Iqbal; Saltanat Aghayeva (Genetic Resources and Crop Evolution, 2025)

Microplastic Pollution: Sources, Degradation Mechanisms, Analytical Advances, and Mitigation Strategies for Environmental Sustainability - Najwa Ibrahim; Amir Muhammad Noh Amin Abdul Rahman; Mohamad Danial Shafiq; Zainovia Lockman; Mariatti Jaafar; Yutaka Kameda (Reviews of Environmental Contamination and Toxicology, 2025)

Aspergillus spp and aflatoxins in Pakistani rice: A case study on the decontamination effect of accelerated aging and improved storage practices - Iqra Naeem; Amir Ismail; Yun Yun Gong; Muhammad Riaz; Aneela Hameed; Mubashir Aziz; Asif Mahmood; Waheed Al Masry; Muhammad Latif; Sher Ali; Carlos Augusto Fernandes de Oliveira (Toxicon, 2025)

Development of a Novel Composite Catalyst containing Renewable Biochar blended with Zinc Oxide and Copper Diphenyl Amine for Visible Light Photocatalytic Degradation of Methylene Blue - Muhammad Raashid; Muhammad Zain Akram; Mohsin Kazmi; Kashaf Imran; Amir Ikhlaq; Muhammad Bin Saeed; Naveed Ramzan; Zafar Masood (Water, Air, & Soil Pollution, 2025)

Sustainable cementless concrete reinforced with recycled steel fibers for spun-cast precast pipes: an innovative solution - Safeer Abbas; Moncef Nehdi; Ali Ahmed; Muhammad Abdullah Khan; Muhammad Mubashir Ajmal; Ammad Amir; Muhammad Zain Kashif; Qura tul Ain (Innovative Infrastructure Solutions, 2025)

Glyceraldehyde-3-phosphate dehydrogenase facilitates Mycoplasma synoviae colonisation in the lower respiratory system - Sahar Zare; Marc S. Marenda; Sathya N. Kulappu Arachchige; Pollob Shil; Muhammad A. Shahid; Somayeh Kordafshari; Chathuri H. Rodrigo; Amin Kawarizadeh; Denise O’Rourke; Amir H. Noormohammadi (Veterinary Microbiology, 2025)

Comprehensive investigation of the smouldering characteristics of hemic peat under varying moisture conditions and the combined influence of wind velocity and direction - Nor Azizah Che Azmi; Ahmad Safuan A Rashid; Nazirah Mohd Apandi; Abd Wahid Rasib; Mohd Nazri Mohd Nasir; Adnan Zainorabidin; Mohamad Sofi Mohamed; Muhammad Amir Mat Shah; Diana Che Lat; Afiqah Ismail (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Oral adjuvanted Vibrio vaccine enhances antibody production and lysozyme activity in the serum and mucus of marine-cultured red hybrid tilapia (Oreochromis sp.) against V. harveyi and V. alginolyticus - Tilusha Manchanayake; Aslah Mohamad; Zahaludin Amir-Danial; Nadirah Abu Nor; Chin Yong-Kit; Muhammad Farhan Nazarudin; Roslindawani Md Nor; Qistina Hasnan; Mohd Zamri-Saad; Mohammad Noor Azmai Amal; Md Yasin Ina-Salwany; Annas Salleh (Fish & Shellfish Immunology, 2025)

Advancing Heavy Metal Removal from Industrial Wastewater Using Oil Palm Waste–Based Adsorbent: toward Efficient Adsorption and Commercialization - Mohd Amir Asyraf Mohd Hamzah; Norhaniza Yusof; Muhammad Abbas Ahmad Zaini; Zainul Akmar Zakaria; Juhana Jaafar; Nurasyikin Misdan (Current Pollution Reports, 2025)
Purpose of Review The palm oil industry, as the largest producer of edible oil in the world, generates considerable volumes of biomass waste, including oil palm fronds, trunks, empty fruit bunches, mesocarp fibers, palm kernel shells, and palm oil fuel ash. Improper disposal of these residues contributes to environmental pollution and resource management challenges. This review aims to critically evaluate recent developments in transforming oil palm biomass waste (OPW) into low-cost, high-performance adsorbents for the removal of heavy metals from industrial wastewater, while aligning with zero-waste and circular economy goals. Recent Findings Recent studies have demonstrated that OPW-derived adsorbents, when subjected to particle size reduction and surface functionalization, exhibit significantly enhanced adsorption capacity and recovery efficiency. Notably, activated carbon nanoparticles derived from empty fruit bunch via KOH activation have demonstrated adsorption capacities exceeding 1000 mg/g for Cu 2+ and Pb 2+ , attributed to their ultrafine size and high surface reactivity. These materials also show strong reusability, with over 80% adsorption efficiency retained after multiple regeneration cycles. Integration of OPW adsorbents into dynamic systems such as fixed-bed columns, adsorption-membrane hybrids, magnetic composites, and gel matrices have been explored to improve operational stability, pollutant removal, and ease of recovery. Summary This review underscores the potential of OPW-derived adsorbents as sustainable and cost-effective alternatives for industrial wastewater treatment. The incorporation of OPW-based materials into engineered systems and the evaluation of post-treatment strategies (e.g., regeneration, reuse, safe disposal) demonstrate their applicability for real-world continuous processes. By promoting the valorization of agricultural waste and addressing current pollution control needs, these materials contribute to improved wastewater management, sustainable resource management, and industrial circularity in palm oil–producing regions. The findings offer valuable insights for environmental managers, policymakers, and industries in adopting circular economy practices and eco-friendly pollution control solutions.

Retraction notice to “Comparative study of ozonation and ozonation catalyzed by Fe-loaded biochar as catalyst to remove methylene blue from aqueous solution” [Chemosphere 307 Part 1, November 2022, 135738] - Muhammad Babar; Hafiz Muhammad Shahzad Munir; Aamna Nawaz; Naveed Ramzan; Umair Azhar; Muhammad Sagir; Muhammad Suleman Tahir; Amir Ikhlaq; Siti Nuurul huda Mohammad Azmin; Muhammad Mubashir; Kuan Shiong Khoo; Kit Wayne Chew (Chemosphere, 2025)

Evaluating the cooling potential of urban green spaces in Faisalabad integrating invest urban cooling model with multisource remote sensing data - Hafiz Abdul Basit Zaid; Usman Mahmood Mughal; Muhammad Amin; Meer Muhammad Sajjad; Muhammad Farhan; Amir Sattar; Shujaat Ali; Mujtaba Ali; Qurat ul Ain (Theoretical and Applied Climatology, 2025)

Effect of Different Levels of Copper Oxide (CuO) Nanoparticles and Biochar on Soil’s Microbial Activities and Maize (Zea Mays L.) Growth - Muhammad Abdullah Aziz; Sana Zahra; Bilal Adil; Amir Naserin; Muhammad Asad Hameed; Ijaz Ali; Temoor Ahmed; Ajaz Ahmad (Journal of Soil Science and Plant Nutrition, 2025)

Distribution modelling and future prediction of a threatened species - Heracleum candicans Wall. ex DC.; Within the framework of biotic and abiotic interactions - Jawad Hussain; Shujaul Mulk Khan; Muhammad Shakeel Khan; Zafeer Saqib; Abdullah; Zeeshan Ahmad; Maria Shah; Nazir Mohammad; Zareena Batool; Amir Sohail; Jie Liu (Journal of Environmental Management, 2025)

A computational analysis of the media coverage of the European Parliament's ‘green' Designation on sustainable energy and climate change - Ileana Zeler; Joan Ramon Rodriguez-Amat; Riasat Muhammad Amir (Energy Policy, 2025)

The effect of chronic microplastic exposure on the growth, biochemical responses, and histological changes of the juvenile sea cucumber Holothuria scabra - Sarah Syazwani Shukhairi; Nurzafirah Mazlan; Nur Nashrah Abd Rahman; Muhammad Nor Afdall Nazahuddin; Amir Syazwan Shawel; Vijay Subbiah Kumar (Environmental Science and Pollution Research, 2025)
Microplastics (MPs) are minuscule plastic particles less than 5 mm in size, originating from the degradation of larger plastic debris. MPs originate from various sources and pose a significant threat to the marine ecosystem. Holothuria scabra is a species of sea cucumber with high commercial value and among the organisms affected by MPs pollution. H. scabra are also crucial in maintaining a clean seabed and recycling nutrients in the ocean ecosystem. Polymethymethacrylate (PMMA), a durable and transparent plastic polymer widely used as a glass alternative in maritime and other industries. This research aimed to investigate the toxicity effects of polymethylmethacrylate-MPs on the well-being of juvenile sea cucumber H. scabra . Over a 60-day treatment period, polymethylmethacrylate MPs were exposed to the juvenile sea cucumber diet at concentrations of 0.6 MPs/g (Treatment 1), 1.2 MPs/g (Treatment 2), and 10 MPs/g (Treatment 3) while a control group which received no MPs exposure to observe changes in their growth, biochemical responses, and histological alteration. The mean weight, weight gain percentage and specific growth rate exhibited significant differences ( p < 0.05) with the control group displaying the highest SGR value of 1.22 ± 0.35%. Mortality was observed in treatment 2 and 3, respectively. A disruption in enzyme activity was also observed across all treatment groups ( p < 0.05). The findings of growth rates and biochemical responses were further supported by histological observation, uncovering injuries and loss of cellular components in respiratory trees and intestines. This study enhances our understanding of the toxicity mechanism associated with PMMA-MPs in deposit feeder organisms.

A new labdane diterpenoid, in vitro and in silico cytotoxicity, and protease inhibitory effects of phytochemicals from Juniperus polycarpos K. Koch leaves - Moslem Naderian; Salar Hafez Ghoran; Muhammad Ikhlas Abdjan; Zahra Sabahi; Soheila Moein; Amir Reza Jassbi; Mahmoodreza Moein (Natural Product Research, 2025)

Tuning electronic properties of NiCo2S4 nanofibers through phosphorous doping for optimized oxygen reduction and evolution reactions in Li-O2 batteries - Sana Shoukat; Yichuan Dou; Mingzhu Gao; Dongning Wan; Muhammad Shoaib; Sikandar Iqbal; Amina Tariq; Irum Rafique; Amir Said; Songze Li; Imran Haider; Jun Wang (Chemical Engineering Journal, 2025)

Overexpression of StDREB30 Gene Enhances Salt Stress Tolerance in Transgenic Potato - Qurat- Ul Ain-Ali; Faiza Munir; Muhammad Faraz Bhatti; Rabia Amir; Alvina Gul (Potato Research, 2025)

The Effects of miR-22-3p on Differentiation of Human Dental Pulp Stem Cells into Neural Progenitor-Like Cells - Muhammad Tehsil Gul; Muhammad Nasir Khan Khattak; Rizwan Qaisar; Manju Nidagodu Jayakumar; A. B. Rani Samsudin; Amir Ali Khan (Molecular Neurobiology, 2025)

Correction: Microscopic investigations of pollen morphological research of selected melliferous taxa; honeybees pollinators-plant interactions - Ateef Ullah; Mushtaq Ahmad; Shabir Ahmad; Hussain Shah; Tehsin Ullah; Muhammad Abdullah; Khalid Mashay Al-Anazi; Mohammad Abul Farah; Rozina; Syed Nohman Gilani; Amir Shahzad; Syed Waseem Gillani; et al. (Genetic Resources and Crop Evolution, 2025)

Quantitative analysis of pathogenesis-related protein expression in Gossypium hirsutum L. to elicitor-induced resistance against cotton leaf curl disease and predicted in-silico protein-protein interactions - Muhammad Fahad Khan; Syed Atif Hasan Naqvi; Adnan Iqbal; Seth Alan Steichen; Amjad Ali; Rana Muhammad Amir Gulzar; Judith K. Brown; Ummad Ud Din Umar (Physiological and Molecular Plant Pathology, 2025)

Occurrence of aflatoxins and effect of preventive practices to inhibit fungal growth and aflatoxin production in leftover flat bread/chapati used as animal feed and stored in Pakistani dairy farms - Mavra Amin; Amir Ismail; Iqra Naeem; Usama Nasir; Muhammad Riaz; Yun Yun Gong; Sher Ali; Michael N. Routledge; Amna Iqbal; Asifa Saif; Carlos Augusto Fernandes Oliveira (Journal of Stored Products Research, 2025)

Textile wastewater treatment by heterogeneous catalytic ozonation using microcellulose loaded ZIF 67 catalyst - Muhammad Fahad Tariq; Farhan Javed; Luigi Rizzo; Muhammad Wasim Tahir; Amir Ikhlaq (Journal of Environmental Management, 2025)

Design of efficient dispase one-bath strategy with low pollution and life cycle assessment for eco-sustainable leather processing - Hui Liu; Zhenhua Yin; Mengya Li; Cuiyun Liu; Muhammad Amir Ali; Jie Liu; Jianming Sun; Keyong Tang; Xinchang Pang (Journal of Environmental Chemical Engineering, 2025)

Exploring the electrochemical potential of MoLa2O4/rGO/Co-MOF nanocomposites in energy storage and monosodium glutamate detection - Nimra Muzaffar; Imad Barsoum; Amir Muhammad Afzal; Muhammad Waqas Iqbal; Zubair Ahmad; Areej S. Alqarni; Shams A.M. Issa; H.M.H. Zakaly (Fuel, 2025)

Comprehensive assessment, intelligent prediction, and precise mitigation strategies for greenhouse gas emissions in full-scale wastewater treatment plants - Zitan Zhang; Fei Qi; Yao Liu; Muhammad Bilal Asif; Amir Ikhlaq; Zhenbei Wang; Caocao Chen; Chen Li; Jing Chang; Qun Li; Ye Li; Yujie Li; et al. (Environmental Research, 2025)

Microscopic investigations of pollen morphological research of selected melliferous taxa; honeybees pollinators-plant interactions - Ateef Ullah; Mushtaq Ahmad; Shabir Ahmad; Hussain Shah; Tehsin Ullah; Muhammad Abdullah; Khalid Mashay Al-Anazi; Mohammad Abul Farah; Rozina; Syed Nohman Gilani; Amir Shahzad; Syed Waseem Gillani; et al. (Genetic Resources and Crop Evolution, 2025)

Comparative Analysis of Heavy Metals and Minerals in Dairy and Plant-Based Milk Alternatives Available in Pakistan’s Markets - Aiman Usman; Sadaf Yaqoob; Hamza Shafiq; Mamoona Amir; Muhammad Riaz; Kousar Parveen; Usama Usman (Biological Trace Element Research, 2025)

Seasonal Variations in Potable Water Quality of Bahawalpur City: A Comprehensive Assessment of Major Ions, Organic Matter, and Disinfection Byproducts - Sundas Kali; Mazhar Iqbal Zafar; Abida Farooqi; Muhammad Saifullah; Sajida Rasheed; Muhammad Bilal khan Niazi; Amir Waseem; Luiza C. Campos (Environmental Monitoring and Assessment, 2025)

Pomegranate peel extract as a sustainable plant protection agent against Xanthomonas campestris pv. campestris: mechanisms and applications - Muhammad Amir Muawiya; Daniele Schiavi; Domenico Rongai; Stefano Giovagnoli; Emidio Camaioni; Giorgio Mariano Balestra (Journal of Plant Pathology, 2025)

Potential role of inoculum size in biomass accumulation and antioxidant secondary metabolites production in adventitious root cultures of Stevia rebaudiana - Naveed Ahmad; Nisar Ahmad; Muhammad Sajid; Kamran Rauf; Mudassar Iqbal; Muhammad Numan; Irfan Ullah; Amir Khan; Wahidah H. Al-Qahtani; Mostafa A. Abdel-Maksoud; Hamada AbdElgawad; Babar Iqbal; et al. (Plant Biosystems, 2025)

Theodorus spiral concept for pico-scale crossflow turbine nozzle design by computational method - Dendy Adanta; Dewi Puspita Sari; Imam Syofii; Farhan Yadi; Amir Arifin; Irsyadi Yani; Muhammad Wafiq Syadhefi; Ahmad Fudholi; Fazila Mohd-Zawawi (Ocean Engineering, 2025)

Thermal performance improvement of a solar distillation system using a spiral coil condenser with a parabolic dish - Muhammad Amin; Hamdani Umar; Teuku Azuar Rizal; Fazri Amir; Nasruddin A. Abdullah; Suma Fachruri Ginting; T.M. Indra Mahlia (Journal of Water Process Engineering, 2025)

Global progress towards the Coal: Tracking coal reserves, coal prices, electricity from coal, carbon emissions and coal phase-out - Muhammad Amir Raza; Abdul Karim; M.M. Aman; Mahmoud Ahmad Al-Khasawneh; Muhammad Faheem (Gondwana Research, 2025)

Designing of efficient CoLa2O4/V-Ag-MOF hybrid electrode for energy storage, hydrogen evolution reaction, and chemical sensors - Asad Ur Rehman; Nimra Muzaffar; Imad Barsoum; Amir Muhammad Afzal; Muhammad Ali; Muhammad Waqas Iqbal; Zubair Ahmad; Sohail Mumtaz; Aboud Ahmed Awadh Bahajjaj; Shaik Abdul Munnaf (Fuel, 2025)

Unveiling the future: Breakthroughs and innovations in MXene-based electrochemical sensors - Muhammad Khan; Xiaohui Sun; Faisal Attique; Muhammad Tahir Saleh; Naveed Ahmad; Kainat Atiq; Muhammad Shafi; Inas A. Ahmed; Imad Barsoum; Muhammad Shahbaz Rafique; Azeem Ullah; Amjad Hussain; et al. (Chemical Engineering Journal, 2025)

Visible light active CdS/CuO nanocomposites for photocatalytic degradation of ciprofloxacin, H2 production and antimicrobial activity - Naveed Akhtar; Chaejin Choi; Muhammad Ateeq; Perveen Fazil; Noor S. Shah; Javed Ali Khan; Abdullah G. Al-Sehemi; Amir Zada; Muhammad Ishaq Ali Shah; Rabia Ikram; Changseok Han (Chemical Engineering Journal, 2025)

Carbon dioxide, global boiling, and climate carnage, from generation to assimilation, photocatalytic conversion to renewable fuels, and mechanism - Muhammad Khan; Xiaohui Sun; Amir Zada; Shohreh Azizi; Muhammad Ishaq Ali Shah; Javed Ali Khan; Ahmed H. Ragab; Mostafa A. Taher; Qumber Abbas; Changseok Han (Science of The Total Environment, 2025)

Periphyton biofilms formulation and application for the removal of trace pollutants from water - Khurram Shahzad; Shahid Mahmood; Azeem Khalid; Rai Muhammad Amir; Rab Nawaz; Marlia Mohd Hanfiah; Zaini Bin Sakawi; Muzammil Anjum (International Biodeterioration & Biodegradation, 2025)

Grass fields play a greater role in maintaining avian biodiversity in urban landscapes than roadsides - H. M. Bichi; Badrul Azhar; Muhammad Syafiq Yahya; Muhamad Amir Hadi; A. A. Ogunjinmi; Norizah Kamarudin; Ahmad R. Norhisham (Urban Ecosystems, 2025)

Non-effervescent Polymeric Floating Tablets of Clarithromycin and Pantoprazole: Preparation and In-Vitro Evaluation for Improved Gastric Drug Retention - Fahad Ashraf; Kifayat Ullah Shah; Muhammad Danish Saeed; Faiqa Falak Naz; Fahad Y. Sabei; Tahseen Ahmed; Syed Shafqat Ali Shah; Amir Badshah; Naeem Ur Rehman; Kausar Ali Mahsud (Journal of Pharmaceutical Innovation, 2025)

Financing the green transition: how green finance, green innovation, green growth, and environmental taxes can drive carbon neutrality - Zhang Wei; Amir Iqbal; Sayeda Jahangir; Muhammad Sibt e Ali; Muttahir Hussain (Environment, Development and Sustainability, 2025)

Bio-catalytic activity of novel poly(ethylene glycol) methacrylate hybridized silver nanomaterials - Natasha Anwar; Mohib Shah; Saad Haroon Anwar; Muhammad Ishaq Ali Shah; Amir Zada; Hammad Ahmad Jan; Abeer Hashem; Graciela Dolores Avila-Quezada; Elsayed Fathi Abd-Allah (South African Journal of Botany, 2025)

A multi-proxy approach to explore paleoenvironmental oscillations and chronostratigraphy of Thanetian carbonates in Eastern Tethys, Pakistan - Amir Shahzad; Yasir Sirfraz; Khawaja Shoaib Ahmed; Muhammad Hanif; Muhammad Tayyib Riaz; Khawaja Shafique Ahmad; Thierry Adatte (Marine and Petroleum Geology, 2025)

Remediation of textile wastewater by hybrid technique using ZIF-67 catalyzed ozonation coupled with electrocoagulation - Farhan Javed; Muhammad Fahad Tariq; Amir Ikhlaq; Hafiz Muhammad Shahzad Munir; Ali Altaee (Journal of Water Process Engineering, 2025)

Development of Cellulose Acetate-Polyethylene Glycol-Chitosan Membrane-Embedded TiO2 Nanoparticles for Reverse Osmosis Desalination - Faizal Mustapa; Selvia Laki Wawe; La Ode Ahmad; Dwiprayogo Wibowo; Amir Mahmud; Maulidiyah Maulidiyah; Akrajas Ali Umar; Muhammad Nurdin (Water, Air, & Soil Pollution, 2025)

Evaluation of Microplastics Ingested by Sea Cucumber Holothuria Scabra from Pulau Jambongan, Sabah - Sarah Syazwani Shukhairi; Nurzafirah Mazlan; Vijay Kumar Subbiah; Nur Nashrah Abd Rahman; Muhammad Nor Afdall Nazahuddin; Amir Syazwan Shawel; Audrey Daning Tuzan; Sitti Raehanah Muhammad Shaleh; Norfazreena Mohd Faudzi; Rossita Shapawi; Muhammad Dawood Shah; Tze Young Thung (Bulletin of Environmental Contamination and Toxicology, 2025)

Exploring the chemistry of waste eggshells and its diverse applications - Laiba Iftikhar; Iqbal Ahmad; Muhammad Saleem; Aamir Rasheed; Amir Waseem (Waste Management, 2024)

Systematic review on buparvaquone resistance associated with non-synonymous mutation in drug binding genes site of Theileria annulate - Muhammad Rashid; Muhammad Hassan Hayat; Naveed Zahra; Mian Sayed Khan; Suleman; Muhammad Nadeem; Tauseef ur Rehman; Muhammad Ehsan; Muhammad Irfan Malik; Muhammad Kashif Obaid; Amir Bakhsh; Mohamed Aziz Darghouth; et al. (Veterinary Parasitology, 2024)

Electronic, thermoelectric and magnetic properties of ternary telluride KAlTe2 and KInTe2 from theoretical perspective - Zahid Ullah; Muhammad Amir; Aiman Bazilla; Salim Ullah; Umar Shahzad; Nazir Ullah; Jabir Khan; Sabahat Gul (Next Research, 2024)

Health risk assessment of lead and cadmium exposure from food and snuff in Pakistani population - Hamza Shafiq; Mamoona Amir; Salman Asghar; Aneela Hameed; Muhammad Riaz (Journal of Trace Elements in Medicine and Biology, 2024)

Biochar and PGPR: A Winning Combination for Peanut Growth and Nodulation under Dry Spell - Tashfeen Alam; Fatima Bibi; Hunaiza Fatima; Faiza Munir; Alvina Gul; Ghulam Haider; Muhammad Jahanzaib; Rabia Amir (Journal of Soil Science and Plant Nutrition, 2024)

In vitro and in vivo efficacy of zinc oxide green nanoparticles against multidrug-resistant Salmonella Typhi - Tasbiha Gul; Lubna Tabassam; Abroo Basharat; Afreenish Amir; Zulqarnain Baqar; Muhammad Jawad Khan (Brazilian Journal of Microbiology, 2024)

Enhanced cadmium immobilization in soil using Fe- and Zn-doped biochar: Mechanisms and safety implications for Cicer arietinum L - Uzma Muzaffar; Muhammad Naveed; Zainab Naseem; Iqra Abid; Kashif Zulfiqar Amir; Saud Alamri; Muhammad Siddique; Martin Brtnicky; Adnan Mustafa (Chemosphere, 2024)

Corrigendum to “Enhancing bird conservation in tropical urban parks through land sparing and sharing strategies: Evidence from occupancy data” [Urban For. Urban Green. 98 (2024) 128415] - Muhamad Amir Hadi; Satya Narayana; Muhammad Syafiq Yahya; Syari Jamian; Alex M. Lechner; Badrul Azhar (Urban Forestry & Urban Greening, 2024)

Exploring fruit ripening methods: Conventional, artificial, and novel approaches for quality and health - Usama Nasir; Amir Ismail; Muhammad Riaz; Kashif Razzaq; Sajid Ali; Ajaz Hussain; Mavra Ameen; Asifa Saif; Farwa Aslam; Carlos Augusto Fernandes de Oliveira (Food Control, 2024)

Failure mechanism of a massive fault–controlled rainfall–triggered landslide in northern Pakistan - Muhammad Tayyib Riaz; Muhammad Basharat; Khawaja Shoaib Ahmed; Yasir Sirfraz; Amir Shahzad; Nisar Ali Shah (Landslides, 2024)

Construction of visible-light-driven 2D/2D NiFe2O4/g-C3N4 Z-scheme heterojunction photocatalyst for effective degradation of organic pollutants and CO2 reduction - Wisal Muhammad; Wajid Ali; Muhammad Asif Khan; Fawad Ali; Amir Zada; Muhammad Zaka Ansar; Pow-Seng Yap (Journal of Environmental Chemical Engineering, 2024)

Enhancing bird conservation in tropical urban parks through land sparing and sharing strategies: Evidence from occupancy data - Muhamad Amir Hadi; Satya Narayana; Muhammad Syafiq Yahya; Syari Jamian; Alex M. Lechner; Badrul Azhar (Urban Forestry & Urban Greening, 2024)

A three-step modification of the DRASTIC model using spatial multi criteria decision making methods to assess groundwater vulnerability - Ali Miron Baki; Seyed Morsal Ghavami; Seyed Amir Muhammad Qureshi; Omid Ghaffari (Groundwater for Sustainable Development, 2024)

Retraction Note: Novel mannich-based derivative of 2-mercaptobenzimidazole (AK7): a new candidate for the treatment of inflammatory arthritis owing to its NF-κB1 inhibitory potential - Gagun Kamran; Hafiz Amir Ali Kharl; Muhammad Nasir Hayat Malik; Waqas Younis; Humaira Nadeem; Aymun Madni Zubair; Muhammad Atif Hayat Malik; Shah Jahan; Ishtiaq Ahmed; Ramla Shabbir; Asma Akram; Irfan Anjum; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Site occupancy of native terrestrial mammals in oil palm landscapes is driven by the synergy of land sparing and sharing strategies - Satya Narayana; Amir Affandi; Muhammad Syafiq Yahya; Kamil Azmi Tohiran; Asrulsani Jambari; Ahmad Razi Norhisham; Badrul Azhar (Journal for Nature Conservation, 2024)

Aflatoxins in the rice production chain: A review on prevalence, detection, and decontamination strategies - Iqra Naeem; Amir Ismail; Muhammad Riaz; Mubashir Aziz; Kashif Akram; Muhammad A. Shahzad; Mavra Ameen; Sher Ali; Carlos A.F. Oliveira (Food Research International, 2024)

Florfenicol removal from veterinary pharmaceutical effluents: Tri-metallic zeolite 5A° for electrochemical oxidation and catalytic ceramic membrane separation - Amir Ikhlaq; Maryam Gull; Afnan Sajid; Khurram Saleem Joya; Muhammad Raashid; Osama Shaheen Rizvi; Zafar Masood; Salman Ahmed; Maryam Abid; Maham Hanif; Hafiz Abdul Aziz; Thamer Abdulhameed Al Johani; et al. (Journal of Environmental Chemical Engineering, 2024)

An Insight on the Rising Trends in Telemedicine and Health - Zobia Tabassum; Sara Rahman; Muhammad Tahir Iqbal; Sidra Amir; Amna Siddiqui (Annals of Biomedical Engineering, 2024)

CamTrapAsia : A dataset of tropical forest vertebrate communities from 239 camera trapping studies - Calebe P. Mendes; Wido R. Albert; Zachary Amir; Marc Ancrenaz; Eric Ash; Badrul Azhar; Henry Bernard; Jedediah Brodie; Tom Bruce; Elliot Carr; Gopalasamy Reuben Clements; Glyn Davies; et al. (Ecology, 2024)
Information on tropical Asian vertebrates has traditionally been sparse, particularly when it comes to cryptic species inhabiting the dense forests of the region. Vertebrate populations are declining globally due to land‐use change and hunting, the latter frequently referred as “defaunation.” This is especially true in tropical Asia where there is extensive land‐use change and high human densities. Robust monitoring requires that large volumes of vertebrate population data be made available for use by the scientific and applied communities. Camera traps have emerged as an effective, non‐invasive, widespread, and common approach to surveying vertebrates in their natural habitats. However, camera‐derived datasets remain scattered across a wide array of sources, including published scientific literature, gray literature, and unpublished works, making it challenging for researchers to harness the full potential of cameras for ecology, conservation, and management. In response, we collated and standardized observations from 239 camera trap studies conducted in tropical Asia. There were 278,260 independent records of 371 distinct species, comprising 232 mammals, 132 birds, and seven reptiles. The total trapping effort accumulated in this data paper consisted of 876,606 trap nights, distributed among Indonesia, Singapore, Malaysia, Bhutan, Thailand, Myanmar, Cambodia, Laos, Vietnam, Nepal, and far eastern India. The relatively standardized deployment methods in the region provide a consistent, reliable, and rich count data set relative to other large‐scale pressence‐only data sets, such as the Global Biodiversity Information Facility (GBIF) or citizen science repositories (e.g., iNaturalist), and is thus most similar to eBird. To facilitate the use of these data, we also provide mammalian species trait information and 13 environmental covariates calculated at three spatial scales around the camera survey centroids (within 10‐, 20‐, and 30‐km buffers). We will update the dataset to include broader coverage of temperate Asia and add newer surveys and covariates as they become available. This dataset unlocks immense opportunities for single‐species ecological or conservation studies as well as applied ecology, community ecology, and macroecology investigations. The data are fully available to the public for utilization and research. Please cite this data paper when utilizing the data.

Exposure to zinc oxide nanoparticles induced reproductive toxicities in male Sprague Dawley rats - Nagina Rehman; Farhat Jabeen; Muhammad Asad; Aneela Nijabat; Amir Ali; Safir Ullah Khan; Juan Pedro Luna-Arias; Zia-ur-Rehman Mashwani; Ayesha Siddiqa; Adhimoolam Karthikeyan; Ajaz Ahmad (Journal of Trace Elements in Medicine and Biology, 2024)

AquMADE: A GIS-based web application to assess groundwater quality by introducing a risk-based irrigation water quality index (RB-IWQI) - Seyed Amir Muhammad Qureshi; Seyed Morsal Ghavami (Environmental Modelling & Software, 2024)

Ce-TiO2 nanoparticles with surface-confined Ce3+/Ce4+ redox pairs for rapid sunlight-driven elimination of organic contaminants from water - Amna Jamil; Tehzeeb Sawaira; Asghar Ali; Muhammad Awais; Amir Habib; Tajamal Hussain; Ahsan Sharif; Naseer Iqbal; Adeel Afzal (Environmental Nanotechnology, Monitoring & Management, 2024)

Diversity, richness, and evenness of birds in Rana Resort Forest, District Kasur, Punjab, Pakistan - Muhammad Amir Sial (Environmental Monitoring and Assessment, 2024)

The therapeutic effect of BODIPY-based photosensitizers against acetylcholinesterase for the treatment of Alzheimer’s disease - Mushtaq Ahmed; Nadia Mushtaq; Naila Sher; Rahmat Ali Khan; Muhammad Amir Masood (Journal of Proteins and Proteomics, 2024)

Mapping the low tolerance factor Bi(Li1/3Zr2/3)O3 end member and MPB composition nexus in Bi1/2Na1/2TiO3-based ceramics - Sabir Ali; Muhammad Sheeraz; Aman Ullah; Won Seok Yun; Amir Ullah; Ill Won Kim; Chang Won Ahn (Chemical Engineering Journal, 2024)

Multi-Elemental Chemostratigraphy, Sequence Development, Depositional History, and Environmental Importance of Early Eocene Red Beds (Kuldana Formation) in NW Himalayas, Pakistan - Amir Shahzad; George Kontakiotis; Thierry Adatte; Khawaja Shoaib Ahmed; Muhammad Tayyib Riaz; Hammad Tariq Janjuhah; Evangelia Besiou (Journal of Earth Science, 2024)

Removal of reactive dyes from textile industrial effluent using electrocoagulation in different parametric conditions of aluminum electrodes - Abdul Mannan Zafar; Asma Naeem; Muhammad Athar Minhas; Muhammad Jamal Hasan; Sania Rafique; Amir Ikhlaq (Total Environment Advances, 2024)

Empirical linkages among financial development, digital infrastructure, energy transition and natural resources footprints in BRICS region - Fang Hou; Muhammad Amir Khan; Malik Tahir Hayat (Resources Policy, 2024)

Innovative modification process of a natural gas power plant using self-sufficient waste heat recovery and flue gas utilization for a CCHP-methanol generation application: A comprehensive multi-variable feasibility study - Shah Faisal; Amir Abbas; Aboulbaba Eladeb; Manoj Kumar Agrawal; Taseer Muhammad; Mohamed Ayadi; Kaouther Ghachem; Lioua Kolsi; Min Wang; Ahmad Mustafa (Process Safety and Environmental Protection, 2024)

Eocene nannofossils and paleoenvironmental reconstruction of the Kuldana Formation in Yadgar area, Muzaffarabad, northern Pakistan - Amir Shahzad; Jahanzeb Khan; Muhammad Hanif; Claudia Baumgartner-Mora; Yasir Sarfraz; Khawaja Shoaib Ahmed; Muhammad Tayyib Riaz; Peter O. Baumgartner; Munir ul Hassan Munir; Adnan Wazir (Palaeoworld, 2024)

Simulation and comprehensive 4E study of a high-efficient CCHP arrangement utilizing geothermal energy and eco-friendly heat recovery - Tirumala Uday Kumar Nutakki; Lioua Kolsi; Aboulbaba Eladeb; Amir Abbas; M.A. Ahmed; Mohamed Ayadi; Taseer Muhammad; Wenxin Bai (Geothermics, 2024)

Understanding the phenomena of negative vapor flux in Nanophotonics-Enabled solar membrane distillation - Manoj Kumar Sharma; Amir Muhammad; Ze He; Mohammad Younas; Mohammad Sameti; Mashallah Rezakazemi; Qilin Li (Chemical Engineering Journal, 2024)

Evaluation of the microplastics in bivalves and water column at Pantai Teluk Likas, North Borneo, Malaysia - Nur Nashrah Abd Rahman; Nurzafirah Mazlan; Sarah Syazwani Shukhairi; Muhammad Nor Afdall Nazahuddin; Amir Syazwan Shawel; Haniza Harun; Afaf Baktir (Environmental Science and Pollution Research, 2024)

Efficient treatment of veterinary pharmaceutical industrial wastewater by catalytic ozonation process: degradation of enrofloxacin via molecular ozone reactions - Amir Ikhlaq; Zafar Masood; Umair Yaqub Qazi; Muhammad Raashid; Osama Shaheen Rizvi; Hafiz Abdul Aziz; Muhammad Saad; Fei Qi; Rahat Javaid (Environmental Science and Pollution Research, 2024)

Recent trends in wastewater treatment by using metal-organic frameworks (MOFs) and their composites: A critical view-point - Syed Shoaib Ahmad Shah; Manzar Sohail; Ghulam Murtza; Amir Waseem; Aziz ur Rehman; Iftikhar Hussain; Muhammad Sohail Bashir; Saleh S. Alarfaji; Ahmed M. Hassan; Muhammad Altaf Nazir; Muhammad Sufyan Javed; Tayyaba Najam (Chemosphere, 2024)

Comparative efficiency of Geotrichum candidum microcapsules prepared with alginate alone and in combination with other polymers: In vivo evaluation - Imrana Amir; Amina Zuberi; Muhammad Kamran; Muhammad imran; Muhammad Ahmad (Food Hydrocolloids, 2024)

COVID-19 associated mucormycosis (CAM) in Kashan, Iran: clinical presentations, risk factors, management, and outcomes - Mahzad Erami; Omid Raiesi; Mansooreh Momen-Heravi; Hossein Mirhendi; Shima Aboutalebian; Muhammad Ibrahim Getso; Amir Hassan Matini; Amir Hossein Ahsaniarani; Mohsen Ganjizadeh; Hajar Hassani Josheghani; Sasan Amiri; Reza Pakzad; et al. (Infectious Diseases, 2024)

Soil Application of Potassium Maintains Growth, Water Relations, Yield and Seed Quality of Quinoa in Salt Affected Soils - Mehmood Ejaz; Muhammad Amir Bakhtavar; Shahid Iqbal; Mahmood Alam Khan; Raheela Jabeen; Nazish Jabeen; Ali Raza (Journal of Crop Health, 2024)

Contribution to the pollen morphology of Astragalus L. section Aegacantha Bunge (Galegeae-Fabaceae) and its systematic significance - Amjad Khan; Mushtaq Ahmad; Amir Sultan; Zakir Ullah; Khawar Majeed; Tariq Ullah; Muhammad Zafar (Palynology, 2024)

Serological detection of important pepper viruses and characterisation of pepper mild mottle virus in Saudi Arabia - Zaheer Khalid; Mahmoud Ahmed Amer; Muhammad Amir; Khadim Hussain; Ibrahim Al-Shahwan; Mohammed Ali Al-Saleh (Australasian Plant Pathology, 2024)

New insights on designing the next-generation materials for electrochemical synthesis of reactive oxidative species towards efficient and scalable water treatment: A review and perspectives - Amir Taqieddin; Stephanie Sarrouf; Muhammad Fahad Ehsan; Akram N. Alshawabkeh (Journal of Environmental Chemical Engineering, 2023)

CA/PEG/chitosan membrane incorporated with TiO2 nanoparticles for strengthening and permselectivity membrane for reverse osmosis desalination - Dwiprayogo Wibowo; Faizal Mustapa; S. Selviantori; Muhammad Idris; Amir Mahmud; Maulidiyah Maulidiyah; Muh. Zakir Muzakkar; Akrajas Ali Umar; Muhammad Nurdin (Environmental Nanotechnology, Monitoring & Management, 2023)

Revolutionizing wastewater treatment with microalgae: Unveiling resource recovery, mechanisms, challenges, and future possibilities - Hassimi Abu Hasan; Mohd Hafizuddin Muhamad; Bin Ji; Nur Aisyah Nazairi; Koh Weng Jiat; Saffi Irdina Sim Wan Azlan Sim; Amir Fitri Muhammad Shafiq Poh (Ecological Engineering, 2023)

Fabrication and Evaluation of Differential Release Bilayer Tablets of Clarithromycin and Levofloxacin by 3D Printing - Qazi Amir Ijaz; Sumera Latif; Sumaira Irum Khan; Memoona Rashid; Hafsa Afzal; Nasrullah Jan; Zeeshan Javaid; Muhammad Sarfraz; Amjad Hussain; Muhammad Sohail Arshad; Nadeem Irfan Bukhari; Nasir Abbas (Journal of Pharmaceutical Innovation, 2023)

Field response and molecular screening of European wheat germplasm against powdery mildew at the Himalayan region of Pakistan - Aamir Iqbal; Zia Ur Rehman; Muhammad Rameez Khan; Amir Muhammad Khan; Shahid Ullah Khan; Muhammad Arif; Javaid Iqbal; Mujeeb Ur Rehman; Minhaj Ali; Muhammad Qasim; Imran Ali; Zakir Hussain Facho; et al. (Journal of Applied Genetics, 2023)

Added value upshot of barley amalgamation in wheat flour to boost the physico-chemical quality attributes of flat bread - Muhammad Abdullah; Muhammad Zulkiffal; Tabussam Tufail; Farah Naz Akbar; Muhammad Owais; Javed Ahmed; Ahsan Javed; Muhammad Ijaz Tabassum; Amna Kanwal; Muhammad Asghar; Muhammad Musa; M. A. Rehman Arif; et al. (Cereal Research Communications, 2023)

Synergistic effect of β-sitosterol and biochar application for improving plant growth of Thymus vulgaris under heat stress - Khadiga Alharbi; Amir Abdullah Khan; Haifa Abdulaziz Sakit Alhaithloul; Nadi Awad Al-Harbi; Salem Mesfir Al-Qahtani; Saeedah Sallum Aloufi; Awatif M. Abdulmajeed; Muhammad Atif Muneer; Suliman M.S. Alghanem; Muhammad Zia-ur-Rehman; Muhammad Usman; Mona H. Soliman (Chemosphere, 2023)

Comprehensive evaluation of hydro-chemical processes, suitability, health risks, and sources of groundwater contamination using compositional data analysis, Nizampur basin, Pakistan - Assad Ullah; Wajid Ali; Said Muhammad; Jehangir Ijaz; Faseeha Amir; Shahid Iqbal (Groundwater for Sustainable Development, 2023)

Nexuses between carbon emissions, trade openness, transport services, globalization index, and growth in China: targeting the sustainable development goals - Li Huang; Muhammad Umer Quddoos; Muhammad Hanif Akhtar; Abdul Haseeb; Muhammad Bashir Khan; Amir Rafique (Environmental Science and Pollution Research, 2023)

Microbe-oriented nanoparticles as phytomedicines for plant health management: An emerging paradigm to achieve global food security - Muhammad Noman; Temoor Ahmed; Usman Ijaz; Amir Hameed; Muhammad Shahid; Azizullah; Dayong Li; Fengming Song (Critical Reviews in Food Science and Nutrition, 2023)

Differential accumulation pattern of cadmium in plant parts of pea varieties in response to varying cadmium levels - Khurram Ziaf; Hafiz Muhammad Talha; Muhammad Awais Ghani; Iftikhar Ahmad; Raheel Anwar; Basharat Ali; Yasir Majeed; Amir Shakeel; Mudassar Iqbal; Abbu Zaid (South African Journal of Botany, 2023)

Examining the role of natural resource rent, environmental regulations, and environmental taxes in sustainable development: Evidence from G-7 economies - Nada Khaddage-Soboh; Adnan Safi; Muhammad Faisal Rasheed; Amir Hasnaoui (Resources Policy, 2023)

Mangrove blue carbon stocks estimation in South Sulawesi Indonesia - Abdul Malik; Abd. Rahim; Abd. Rasyid Jalil; Muhammad Fathurachman Amir; Dary Setiawan Arif; Muhammad Rizal; Justikharah Husain; D'rollins William; Nurul Jihad (Continental Shelf Research, 2023)

Comparative evaluation of different moulting methods on productive performance, egg quality, and antibody response of leghorn hens - Amir Saeed; Shahid Mehmood; Muhammad Shahid Zahoor; Ehsaan Ullah Khan; Muhammad Usman; Syed Ghulam Mohayud Din Hashmi; Kinza Saleem; Sohail Ahmad (Tropical Animal Health and Production, 2023)

Synergistic neuroprotection by phytocompounds of Bacopa monnieri in scopolamine-induced Alzheimer’s disease mice model - Shehla Shoukat; Muhammad Amir Zia; Muhammad Uzair; Roua A. Alsubki; Kaynat Sajid; Sana Shoukat; KOTB A. Attia; Sajid Fiaz; Shaukat Ali; Itoh Kimiko; Ghulam Muhammad Ali (Molecular Biology Reports, 2023)

Improving bio aviation fuel yield from biogenic carbon sources through electrolysis assisted chemical looping gasification - Mohammad Shahrivar; Muhammad Nauman Saeed; Gajanan Dattarao Surywanshi; Tobias Mattisson; Amir H. Soleimanisalim (Fuel, 2023)

Date Palm Biochar and Date Palm Activated Carbon as Green Adsorbent—Synthesis and Application - Mona Al Malki; Abu Zahrim Yaser; Mohd. Amir Asyraf Mohd. Hamzah; Muhammad Abbas Ahmad Zaini; Nurzila Ab. Latif; Siti Halimah Hasmoni; Zainul Akmar Zakaria (Current Pollution Reports, 2023)

Holistic expression of miR-17-92 cluster in obesity, kidney diseases, cardiovascular diseases, and diabetes - Maheen Ejaz; Syed Mohammad Usman; Saira Amir; Muhammad Jawad Khan (Molecular Biology Reports, 2023)

Application of teleseismic receiver functions and gravity for Moho depth mapping: a case study of the Western Himalayas - Mohammad Salam; Jamil Ahmad; Waqar Ali Zafar; Muhammad Tahir Iqbal; Imran Khan; Amir Sultan; Talat Iqbal (Arabian Journal of Geosciences, 2023)

Impact of pollution prevention strategies on environment sustainability: role of environmental management accounting and environmental proactivity - Kamran Ali; Naila Kausar; Muhammad Amir (Environmental Science and Pollution Research, 2023)

Characterization of the layered SIF distribution through hyperspectral observation and SCOPE modeling for a subtropical evergreen forest - Kai Zhu; Jinghua Chen; Shaoqiang Wang; Hongliang Fang; Bin Chen; Leiming Zhang; Yuelin Li; Chen Zheng; Muhammad Amir (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Unlocking green growth: an ARDL estimation of pollution prevention practices for economic and environmental sustainability - Muhammad Amir; Muhammad Siddique Malik; Kamran Ali (Environment, Development and Sustainability, 2023)

Sedimentological, Diagenetic, and Sequence Stratigraphic Controls on the Shallow to Marginal Marine Carbonates of the Middle Jurassic Samana Suk Formation, North Pakistan - Shazia Qamar; Mumtaz Muhammad Shah; Hammad Tariq Janjuhah; George Kontakiotis; Amir Shahzad; Evangelia Besiou (Journal of Marine Science and Engineering, 2023)
This study presents a thorough analysis of the sedimentology, diagenesis, and sequence stratigraphy of the Middle Jurassic Samana Suk Formation in the Hazara Basin of northern Pakistan. Focusing on two sections, namely Mera Rehmat and Por Miana, the research aims to unravel the complex geological processes within the formation. The examination of microfacies reveals nine distinct depositional textures, ranging from mudstone to wackestone, packstone, and grainstone, indicating various inner ramp environments such as open marine, lagoon, and coastal settings. Petrographic investigations shed light on diagenetic processes, including micritization, cementation, dissolution, compaction, neomorphism, and dolomitization. Six cementation types are identified, and the dolomitization patterns vary, providing insights into lagoonal environments and mudstone replacement. Sequence stratigraphic analysis uncovers intriguing patterns within the Samana Suk Formation. The high-stand system tract is characterized by mudstones, pelloidal grainstones, and dolomitized mudstones, indicating periods of high sea level. In contrast, the transgressive system tract displays ooidal grainstones, pelloidal packstones, and pel-bioclastic grainstones, representing transgression and inundation of previously exposed areas. A significant finding is the impact of diagenesis on reservoir quality parameters, specifically porosity, and permeability. Diagenetic processes, cementation types, and dolomitization patterns have significantly altered the pore network, highlighting the importance of considering diagenesis in assessing the Samana Suk Formation as a hydrocarbon reservoir. This research provides a comprehensive understanding of the sedimentology, diagenesis, and sequence stratigraphy of the Middle Jurassic Samana Suk Formation. The findings contribute to our knowledge of similar carbonate reservoirs globally, enhancing the exploration and development of hydrocarbon resources in comparable depositional environments.

Dyeing of wool fabric with natural dye extracted from Dalbergia Sissoo using natural mordants - Kashif Iqbal; Haseeb Afzal; Muhammad Owais Raza Siddiqui; Uzma Bashir; Khayale Jan; Amir Abbas; Hafiz Affan Abid (Sustainable Chemistry and Pharmacy, 2023)

Biocompatible cellulose acetate supported ammonium based ionic liquid membranes; way forward to remediate water pollution - Amina Khalid; Sana Zulfiqar; Noshabah Tabassum; Amir Sada Khan; Muhammad Amin Abid; Muhammad Saeed Akhtar; Fahad Al-Misned; Ahmed Muteb Aljuwayid; Sasan Zahmatkesh; Saira Asif (Chemosphere, 2023)

Phytotoxic responses of wheat to an imidazolium based ionic liquid in absence and presence of biochar - Taza Gul; Muhammad Mudasar Aslam; Amir Sada Khan; Tahir Iqbal; Faizan Ullah; Gaber E. Eldesoky; Ahmed Muteb Aljuwayid; Muhammad Saeed Akhtar (Chemosphere, 2023)

Rainfall-driven machine learning models for accurate flood inundation mapping in Karachi, Pakistan - Umair Rasool; Xinan Yin; Zongxue Xu; Roberta Padulano; Muhammad Awais Rasool; Muhammad Amir Siddique; Muhammad Azher Hassan; Venkatramanan Senapathi (Urban Climate, 2023)

Effects of prepartum melatonin treatment and suckling on postpartum reproductive performance of Beetal goats under subtropical conditions - Muhammad Afzaal; Muhammad Irfan-ur-Rehman Khan; Waqas Ahmad; Amir Hayat; Qasir Abbas; Muhammad Arshad; Nasir Hameed; Imran Mohsin; Amjad Riaz (Small Ruminant Research, 2023)

RETRACTED ARTICLE: Novel mannich-based derivative of 2-mercaptobenzimidazole (AK7): a new candidate for the treatment of inflammatory arthritis owing to its NF-κB1 inhibitory potential - Gagun Kamran; Hafiz Amir Ali Kharl; Muhammad Nasir Hayat Malik; Waqas Younis; Humaira Nadeem; Aymun Madni Zubair; Muhammad Atif Hayat Malik; Shah Jahan; Ishtiaq Ahmed; Ramla Shabbir; Asma Akram; Irfan Anjum; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Occurrence and completed genomes of sweet potato chlorotic stunt virus infecting sweet potato in Korea - Nattanong Bupi; Hee-Seong Byun; Aamir Lal; Thuy Thi Bich Vo; Muhammad Amir Qureshi; Eui-Joon Kil; Youngjae Chung; Taek-Kyun Lee; Sukchan Lee (European Journal of Plant Pathology, 2023)

Diversity of hipparionines (Perissodactyla: Equidae) from the late Miocene–Pliocene Siwalik deposits at Haritalyangar, India - Anek Ram Sankhyan; Sayyed Ghyour Abbas; Muhammad Akbar Khan; Muhammad Adeeb Babar; Amir Yasin (Annales de Paléontologie, 2023)

Reconnoitering the capabilities of nodule endophytic Pantoea dispersa for improved nodulation and grain yield of chickpea (Cicer arietinum L.) - Mohsin Tariq; Nayab Hasnain; Ijaz Rasul; Muhammad Azeem Asad; Aqsa Javed; Kamran Rashid; Javeria Shafique; Wajeeha Iram; Amir Hameed; Marriam Zafar (World Journal of Microbiology and Biotechnology, 2023)

Biochar and Selenium Nanoparticles Induce Water Transporter Genes for Sustaining Carbon Assimilation and Grain Production in Salt-Stressed Wheat - Mona H. Soliman; Ghalia S. H. Alnusairi; Amir Abdullah Khan; Taghreed S. Alnusaire; Marwa A. Fakhr; Awatif M. Abdulmajeed; Heshmat S. Aldesuquy; Muhammad Yahya; Ullah Najeeb (Journal of Plant Growth Regulation, 2023)
In a controlled environment experiment, we studied how physiological changes in leaves during the vegetative phase regulate final grain yield of wheat crops in salt-affected soils. We also hypothesized that amendments such as biochar (SB) and selenium-chitosan nanoparticles (Se-NPs) can protect wheat plants from salt injury. 20-day-old wheat plants were submitted to 4-week salt stress (3000 ppm NaCl). Soybean straw biochar was mixed with soil media at planting and Se-NPs (30 ppm) was sprayed 5 days after the first salt stress treatment. At the end of 4-week Se-NPs treatment, one set of plants was harvested for studying leaf level physiological changes. The salt-stressed plants accumulated significantly high leaf Na + (~ 13-fold increase), which trigged oxidative and osmotic damage. This salt-induced cellular injury was evident from significantly high levels of lipid membrane peroxidation and inhibited photosynthesis. Our study suggested that leaf physiological impairment in wheat plants was translated into poor biomass production and grain yield loss at crop maturity. Compared with control, salt-stressed plants produced 43% lesser biomass during vegetative phase, and 62% lesser grain yield at maturity. Amendments such as SB and Se-NPs protected the plants from salt-induced cellular injury by restricting Na + transport toward leaf tissues. Plants treated with NaCl + SB + Se-NPs accumulated 50% less Na + concentrations in leaves compared with NaCl-treated plants. Our study also suggested that SB and Se-NPs can restore ionic homeostasis and carbon assimilation in salt-stressed wheat by upregulating key transporter genes in leaves.

Alginate magnetic graphene oxide biocomposite synthesis for removal of aromatic amines from aqueous samples - Muhammad Amir Zeb; Jasmin Shah; Muhammad Rasul Jan (Environmental Science and Pollution Research, 2023)

A comparative study based on performance and techno-economic analysis of different strategies for PV-Electrolyzer (green) hydrogen fueling incinerator system - Osama Majeed Butt; Muhammad Shakeel Ahmad; Teong Kai Lun; Hang Seng Che; H. Fayaz; Nasrudin Abd Rahim; Krzysztof K.K. Koziol; Neyara Radwan; Mohammad Amir Khan; Nadeem A Khan; Lakhveer Singh (Waste Management, 2023)

The use of magnetic and geoelectrical methods to locate buried ancient artificial canals and wells around the cultural heritage of Indrapatra Fort, Aceh, Indonesia - Nazli Ismail; Muhammad Yanis; Amir Asyqari (Geosciences Journal, 2023)

Assessment of heavy metal pollution using contamination factor, pollution load index, and geoaccumulation index in Kalpani River sediments, Pakistan - Muhammad Jamal Nasir; Abdul Wahab; Tehreem Ayaz; Sardar Khan; Amir Zeb Khan; Ming Lei (Arabian Journal of Geosciences, 2023)

Improving drought mitigation strategies and disaster risk reduction through MODIS and TRMM-based data in relation to climate change over Pakistan - Shahzad Ali; Abdul Basit; Tyan Alice Makanda; Inamullah; Fahim Ullah Khan; Muhammad Sajid; Tamseela Riaz; Hira Farooq Abbasi; Manzoor; Amir Sohail (Environmental Science and Pollution Research, 2023)

Fabrication of hybrid covalent triazine framework-zinc ferrite spinel to uplift visible light–driven photocatalytic organic pollutant degradation - Edy Saputra; Barata Aditya Prawiranegara; Muhammad Wahyu Nugraha; Nonni Soraya Sambudi; Heni Sugesti; Amir Awaluddin; Komalasari; Panca Setia Utama; Maykel Manawan (Environmental Science and Pollution Research, 2023)

Cleaner production of biodiesel from novel non-edible seed oil (Carthamus lanatus L.) via highly reactive and recyclable green nano CoWO3@rGO composite in context of green energy adaptation - Mamoona Munir; Muhammad Saeed; Mushtaq Ahmad; Amir Waseem; Mustafa Alsaady; Saira Asif; Anas Ahmed; Mohd Shariq Khan; Awais Bokhari; Muhammad Mubashir; Lai Fatt Chuah; Pau Loke Show (Fuel, 2023)

Nickel-based nitrodopamine MOF and its derived composites functionalized with multi-walled carbon nanotubes for efficient OER applications - Sonia Kiran; Ghazala Yasmeen; Zahid Shafiq; Amir Abbas; Sumaira Manzoor; Dilshad Hussain; Rami Adel Pashameah; Eman Alzahrani; Abdullah K. Alanazi; Muhammad Naeem Ashiq (Fuel, 2023)

The impact of climate variables on marine fish production: an empirical evidence from Bangladesh based on autoregressive distributed lag (ARDL) approach - Mahfuza Begum; Muhammad Mehedi Masud; Lubna Alam; Mazlin Bin Mokhtar; Ahmad Aldrie Amir (Environmental Science and Pollution Research, 2022)

Mixing tannery effluent had fertilizing effect on growth, nutrient accumulation, and photosynthetic capacity of some cucurbitaceous vegetables: A little help from foe - Muhammad Zaheer; Zafar Ullah Zafar; Habib-ur-Rehman Athar; Hussan Bano; Misbah Amir; Ayesha Khalid; Hamid Manzoor; Muhammad Javed; Muhammad Iqbal; Chukwuma C. Ogbaga; Muhammad Kamran Qureshi (Environmental Science and Pollution Research, 2022)

Correction to: Mechanical performance and environmental impact of normal strength concrete incorporating various levels of coconut fiber and recycled aggregates - Syed Haroon Ali Shah; Muhammad Talha Amir; Babar Ali; Mohamed Hechmi El Ouni (Environmental Science and Pollution Research, 2022)

Mechanical performance and environmental impact of normal strength concrete incorporating various levels of coconut fiber and recycled aggregates - Syed Haroon Ali Shah; Muhammad Talha Amir; Babar Ali; Mohamed Hechmi El Ouni (Environmental Science and Pollution Research, 2022)

Tanneries impact on groundwater quality: a case study of Kasur city in Pakistan - Hafiz Qasim Ali; Muhammad Umair Yasir; Amir Farooq; Mahrukh Khan; Muhammad Salman; Muhammad Waqar (Environmental Monitoring and Assessment, 2022)

Evaluation of agro-morphological traits, seed characterization and genetic diversity of local rice (Oryza sativa L.) varieties of Pakistan - Urooj Fazal; Israr Ud Din; Amir Muhammad Khan; Fahim Ullah Khan; Mudassar Nawaz Khan; Navid Iqbal; Muhammad Ibrahim; Sajid Ali Khan Bangash (Genetic Resources and Crop Evolution, 2022)

Fluid Flow Analysis of Integrated Porous Bone Scaffold and Cancellous Bone at Different Skeletal Sites: In Silico Study - Muhammad Azfar Noordin; Mohamad Ikhwan Kori; Abdul Hadi Abdul Wahab; Ardiyansyah Syahrom; Amir Putra Md Saad (Transport in Porous Media, 2022)

Groundwater quality assessment and its vulnerability to pollution: a study of district Nowshera, Khyber Pakhtunkhwa, Pakistan - Muhammad Jamal Nasir; Muhammad Tufail; Tehreem Ayaz; Sardar Khan; Amir Zeb Khan; Ming Lei (Environmental Monitoring and Assessment, 2022)

Supramolecular solvent–based liquid phase extraction of antimony prior to spectrophotometric quantification - Mansoor Khan; Muhammad Jamshed; Amir Badhshah; Umar Nishan; Mustafa Soylak (Environmental Monitoring and Assessment, 2022)

Triggering mechanisms of Gayari avalanche, Pakistan - Bilal Saif; Mohammad Tahir; Amir Sultan; Muhammad Tahir Iqbal; Talat Iqbal; Muhammad Ali Shah; Samia Gurmani (Natural Hazards, 2022)

A Comparative Analysis of Adopters and Non‐adopters of Drip Irrigation under Plastic Tunnels for Cucumber ( Cucumis sativus L.) Production in Balochistan, Pakistan - Said Qasim; Muhammad Qasim; Anees Hassan; Ghulam Murtaza; Amir Nawaz Khan (Irrigation and Drainage, 2022)
This research tries to compare the water use efficiency, electricity efficiency and economic efficiency of adopters and non‐adopters of drip irrigation under plastic tunnels (DIUPT). Data regarding the socio‐economic conditions of farmers and their views on the advantages and disadvantages of the DIUPT were collected through a questionnaire survey of 200 farmers. For expenses, income, electricity efficiency and water use efficiency, we collected data only from the sample farmers, i.e. one adopter and one non‐adopter. Results also revealed that the total horsepower (HP) hours of water per acre used for drip‐irrigated cucumber under plastic tunnels was 240 compared to 576 HP hours for the flood method of irrigation, thereby saving 58% (336 HP hours) of energy. In other words, with the same amount of water used for irrigating 1 acre of cucumber under flood irrigation, 2.4 acres of cucumber could be irrigated using drip irrigation. Realizing about 51% higher yields under drip irrigation, adopters enjoy 40% higher returns than non‐adopter farmers. The study recommends dissemination of information to farmers about DIUPT through training and seminars. Adoption of these technologies would lead to efficient and sustainable use of already depleting water resources in the drought‐prone province of Balochistan.

Single nucleotide polymorphism based assessment of genetic diversity in local and exotic onion genotypes - Najma Tabussam; Rashid Mehmood Rana; Fahad Masoud Wattoo; Azeem Iqbal Khan; Rai Muhammad Amir; Talha Javed; Sunny Ahmar; Eldessoky S. Dessoky; Nader R. Abdelsalam (Molecular Biology Reports, 2022)

RETRACTED ARTICLE: Novel acetamide derivatives of 2-aminobenzimidazole prevent inflammatory arthritis in rats via suppression of pro-inflammatory mediators - Aymun Madni Zubair; Muhammad Nasir Hayat Malik; Waqas Younis; Muhammad Atif Hayat Malik; Shah Jahan; Ishtiaq Ahmed; Alamgeer Yuchi; Muhammad Naveed Mushtaq; Romeeza Tahir; Muhammad Bilal Sarwar; Muhammad Roman; Ayaz Ali Khan; et al. (Inflammopharmacology, 2022)

Development of Basmati lines by the introgression of three bacterial blight resistant genes through marker-assisted breeding - Allah Ditta Babar; Abha Zaka; Shahzad Amir Naveed; Niaz Ahmad; Kashif Aslam; Muhammad Asif; Umer Maqsood; Casiana M. Vera Cruz; Muhammad Arif (Euphytica, 2022)

Comparative toxic effects of Eucalyptus globulus L. (Myrtales: Myrtaceae) and its green synthesized zinc oxide nanoparticles (ZnONPs) against Rhyzopertha dominica (F.) (Coleoptera: Bostrichidae) - Muhammad Amir Siddique; Mansoor ul Hasan; Muhammad Sagheer; Shahbaz Talib Sahi (International Journal of Tropical Insect Science, 2022)

Feeding niche overlap between native and alien fishes in Swat River, Khyber Pakhtunkhwa, Pakistan - Amir Said; Muhammad Imran; Muhammad Tahir Waseem; Abdul Majid Khan; Noman Khalique; Ghulam Sarwar; Rana Manzoor Ahmad (Environmental Biology of Fishes, 2022)

Correction to: Molecular detection of Cryptosporidium: an emerging parasite in different water sources of 2010 flood‑affected district Nowshera, Pakistan - Shaukat Ali Khan; Imran Khan; Izaz Ali; Amir Muhammad Khan; Muhammad Anees; Khurshaid Ali Khan; Wajid Rashid; Noorul Akbar (Archives of Microbiology, 2022)

Mapping sequences and mineral deposits in poorly exposed lithologies of inaccessible regions in Azad Jammu and Kashmir using SVM with ASTER satellite data - Muhammad Imran; Sultan Ahmad; Amir Sattar; Aqil Tariq (Arabian Journal of Geosciences, 2022)

Re-investigating the nexuses of renewable energy, natural resources and transport services: a roadmap towards sustainable development - Syed Abdul Rehman Khan; Muhammad Umer Quddoos; Muhammad Hanif Akhtar; Amir Rafique; Mustansar Hayat; Saqib Gulzar; Zhang Yu (Environmental Science and Pollution Research, 2022)

Asymmetric relationship of environmental degradation and economic growth with tourism demand in Pakistan: evidence from non-linear ARDL and causality estimation - Muhammad Amir; Muhammad Siddique; Kamran Ali; Azaz Ali Ather Bukhari; Naila Kausar (Environmental Science and Pollution Research, 2022)

Arsenic exposure through drinking groundwater and consuming wastewater-irrigated vegetables in Multan, Pakistan - Mamoona Amir; Salman Asghar; Muhammad Ahsin; Shahid Hussain; Amir Ismail; Muhammad Riaz; Safina Naz (Environmental Geochemistry and Health, 2021)

Preparation and Characterization of pH-Independent Sustained-Release Tablets Containing Hot Melt Extruded Solid Dispersions of Clarithromycin - Qazi Amir Ijaz; Sumera Latif; Qurat-ul-ain Shoaib; Memoona Rashid; Muhammad Sohail Arshad; Amjad Hussain; Nadeem Irfan Bukhari; Sohail Riaz; Nasir Abbas (AAPS PharmSciTech, 2021)

Role of nanotechnology in animal production and veterinary medicine - Ahmad Ali; Muhammad Ijaz; Yasir Razzaq Khan; Hina Afzal Sajid; Kashif Hussain; Ameer Hamza Rabbani; Muhammad Shahid; Omer Naseer; Awais Ghaffar; Muhammad Anas Naeem; Muhammad Zeeshan Zafar; Amir Iftikhar Malik; et al. (Tropical Animal Health and Production, 2021)

The Transition from Arid Farming Systems to Agroforestry Systems in Pakistan: A Comparison of Monetary Returns - Ghulam Abbas; Akhter Ali; Muhammad Khan; Hafiz Zahid Mahmood; Sazali Abdul Wahab; Rafi Amir-ud-Din (Small-scale Forestry, 2021)

Molecular detection of Cryptosporidium: an emerging parasite in different water sources of 2010 flood-affected district Nowshera, Pakistan - Shaukat Ali Khan; Imran Khan; Izaz Ali; Amir Muhammad Khan; Muhammad Anees; Khurshaid Ali Khan; Wajid Rashid; Noorul Akbar (Archives of Microbiology, 2021)

Comparative biogeography and the evolution of population structure for bottlenose and common dolphins in the Indian Ocean - Howard W. I. Gray; Ing Chen; André E. Moura; Ada Natoli; Shin Nishida; Shinsuke Tanabe; Gianna Minton; Louisa S. Ponnampalam; Muhammad S. Kiani; Ross Culloch; Mauvis Gore; Anna Särnblad; et al. (Journal of Biogeography, 2021)
Aim In the marine environment, where there are few physical boundaries to gene flow, there is often nevertheless intraspecific diversity with consequences for effective conservation and management. Here, we compare two closely related dolphin species with a shared distribution in the Indian Ocean (IO) to better understand the biogeographic drivers of their population structure. Location Global oceans and seas with a focus on the Indian Ocean Taxon Tursiops sp. and Delphinus sp. Methods Bayesian, ordination, assignment, statistical and phylogenetic analyses to assess phylogeography, connectivity and population structure using microsatellite and mitochondrial DNA genetic markers. Results Both Tursiops sp. and Delphinus sp. showed population structure across the western IO and, in each case, populations in the Arabian Sea (off India, Pakistan and Oman) were most differentiated. Comparisons with other populations worldwide revealed independent lineages in this geographic region for both genera. For T . aduncus , (for which multiple sites within the IO could be compared), Bayesian modelling best supported a scenario of expansion southwards following a bottleneck event resulting in differentiation between the northern and western IO. For Delphinus, the same pattern is even more pronounced. Populations in the Arabian Sea region of the north‐western IO show genetic isolation for each of the two genera, consistent with other studies of cetacean species in this region. Main conclusions We propose that changes in the intensity of the southwest monsoon during the climate cycles of the Pleistocene could have affected regional patterns of productivity and represent an important biogeographic driver promoting the observed patterns of differentiation and population dynamics seen in our focal species. Patterns of population genetic structure are consistent with phenotypic differences, suggesting an influence from distinct habitats and resources, and emphasising the need for effective conservation measures in this geographic region.

Geotechnical investigation and landslide susceptibility assessment along the Neelum road: a case study from Lesser Himalayas, Pakistan - Khawaja Shoaib Ahmed; Muhammad Basharat; Muhammad Tayyib Riaz; Yasir Sarfraz; Amir Shahzad (Arabian Journal of Geosciences, 2021)

Lead contamination in shooting range soils and its phytoremediation in Pakistan: a greenhouse experiment - Amir Zeb Khan; Sardar Khan; Said Muhammad; Shams Ali Baig; Abdullah Khan; Muhammad Jamal Nasir; Madiha Azhar; Alia Naz (Arabian Journal of Geosciences, 2021)

Dechlorane Plus as an emerging environmental pollutant in Asia: a review - Mazhar Iqbal Zafar; Sundas Kali; Mehtabidah Ali; Muhammad Asam Riaz; Tayyaba Naz; Muhammad Mazhar Iqbal; Noshin Masood; Kashif Munawar; Bilal Jan; Sohail Ahmed; Amir Waseem; Muhammad Bilal Khan Niazi (Environmental Science and Pollution Research, 2020)

Intraperitoneal injections of copper ferrite nanoparticles disturb blood, plasma, and antioxidant parameters of Wistar rats in a sex-specific manner - Hasna Riaz; Rimsha Hashmi; Shairyar Abid; Nisha Shareef; Abida Faqir; Aqsa Amir; Muhammad Saqib Shahzad; Muhammad Shakeel; Saeed Akhtar; Muhammad Naeem Ashiq; Ather Ibrahim; Furhan Iqbal (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Preserving wheat grain quality and preventing aflatoxin accumulation during storage without pesticides using dry chain technology - Muhammad Amir Bakhtavar; Irfan Afzal (Environmental Science and Pollution Research, 2020)

Comparative efficacy of mitigation techniques for the detoxification of Prunus persica (L.) from selected pesticide residues - Neelab; Muhammad Rafique Asi; Sundas Kali; Muhammad Asam Riaz; Amir Waseem; Muhammad Mazhar Iqbal; Nauman Ahmad; Mazhar Iqbal; Noshin Masood; Mazhar Iqbal Zafar (Environmental Science and Pollution Research, 2020)

Halotolerant potassium solubilizing plant growth promoting rhizobacteria may improve potassium availability under saline conditions - Muhammad Ashfaq; Hasnuri Mat Hassan; Amir Hamzah Ahmad Ghazali; Maqshoof Ahmad (Environmental Monitoring and Assessment, 2020)

Projection of vegetation impacts on future droughts over West Africa using a coupled RegCM-CLM-CN-DV - Muhammad Shafqat Mehboob; Yeonjoo Kim; Jaehyeong Lee; Myoung-Jin Um; Amir Erfanian; Guiling Wang (Climatic Change, 2020)

Partial Substitution of Fishmeal with Plant Protein Source the Soybean Meal in the Diets of Arabian Yellowfin Seabream Acanthopagrus arabicus Juveniles - Naveed Ahmad; Jamal Pirzada A. Siddiqui; Ghulam Nabi; Khan Mir Khan; Amjad Ali; Yasmeen Zamir; Mohammad Abdul Momin Siddique; Shabir Ali Amir; Farah Naz Khokhar; Muhammad Amin (Thalassas: An International Journal of Marine Sciences, 2020)

Determinants of farmers’ adaptation to climate change in rain-fed agriculture of Pakistan - Sarah Amir; Zafeer Saqib; Muhammad Irfan Khan; Akhter Ali; Muhammad Azeem Khan; Syed Atif Bokhari; Zaman-ul-Haq (Arabian Journal of Geosciences, 2020)

Antibacterial and antioxidant activity of naphthofuranquinones from the twigs of tropical mangrove Avicennia officinalis - Suvik Assaw; Muhammad Isyraq Hazim Mohd Amir; Tyng Tyng Khaw; Kamariah Bakar; Siti Aisha Mohd Radzi; Noor Wini Mazlan (Natural Product Research, 2020)

Geoinformatics and geophysical survey-based estimation of best groundwater potential sites through surface and subsurface indicators - Umair Rasool; Jianping Chen; Shafi Muhammad; Jamil Siddique; Senapathi Venkatramanan; Chidambaram Sabarathinam; Muhammad Amir Siddique; Muhammad Awais Rasool (Arabian Journal of Geosciences, 2020)

Influence of early rearing environment on water-borne cortisol and expression of stress-related genes in grass carp (Ctenopharyngodon idella) - Mahmood ul Hassan Murtaza; Amina Zuberi; Muhammad Ahmad; Imrana Amir; Muhammad Kamran; Manzoor Ahmad (Molecular Biology Reports, 2020)

Zinc status and its requirement by rural adults consuming wheat from control or zinc-treated fields - Muhammad Ahsin; Shahid Hussain; Zed Rengel; Mamoona Amir (Environmental Geochemistry and Health, 2020)

Human Biomonitoring of Trace Elements in Scalp Hair from Healthy Population of Pakistan - Fouzia Noreen; Ashif Sajjad; Khalid Mahmood; Muhammad Anwar; Manzar Zahra; Amir Waseem (Biological Trace Element Research, 2020)

Environmental risk assessment of diclofenac residues in surface waters and wastewater: a hidden global threat to aquatic ecosystem - Hafsa Hanif; Amir Waseem; Sundas Kali; Naveeda Akhtar Qureshi; Muhammad Majid; Mazhar Iqbal; Tofeeq Ur-Rehman; Muhammad Tahir; Sohail Yousaf; Muhammad Mazhar Iqbal; Imtiaz Ahmad Khan; Mazhar Iqbal Zafar (Environmental Monitoring and Assessment, 2020)

Exogenous Selenium-Instigated Physiochemical Transformations Impart Terminal Heat Tolerance in Bt Cotton - Muhammad Farrukh Saleem; Muhammad Asif Kamal; Muhammad Shahid; Amna Saleem; Amir Shakeel; Shakeel Ahmad Anjum (Journal of Soil Science and Plant Nutrition, 2020)

Photocatalytic Degradation of Congo Red Dye from Aqueous Environment Using Cobalt Ferrite Nanostructures: Development, Characterization, and Photocatalytic Performance - Nisar Ali; Amir Said; Farman Ali; Fazal Raziq; Zarshad Ali; Muhammad Bilal; Laurence Reinert; Tasleem Begum; Hafiz M. N. Iqbal (Water, Air, & Soil Pollution, 2020)

Isolation and functional characterization of an Ethylene Response Factor (RhERF092) from rose (Rosa hybrida) - Muhammad Ali Khan; Muhammad Imtiaz; Adil Hussain; Fazal Jalal; Sikandar Hayat; Sayed Hussain; Fazal Said; Mehboob Alam; Rabia Amir (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Complexing agents for metal removal using ultrafiltration membranes: a review - Mustapha D. Garba; Muhammad Usman; Mohammad A. Jafar Mazumder; Amir Al-Ahmed; Inamuddin (Environmental Chemistry Letters, 2019)

The first report on serotyping of bluetongue virus in small ruminants of Khyber Pakhtunkhwa province, Pakistan - Amir Iftikhar Malik; Muhammad Ijaz; Tahir Yaqub; Muhammad Zubair Shabir; Muhammad Avais; Awais Ghaffar; Ahmad Ali; Shahid Hussain Farooqi; Khalid Mehmood (Tropical Animal Health and Production, 2019)

Social implications of palm oil production through social life cycle perspectives in Johor, Malaysia - Khairul Izzuddin Muhammad; Amir Hamzah Sharaai; Mohd Mansor Ismail; Rosta Harun; Wong Siew Yien (The International Journal of Life Cycle Assessment, 2019)

Infection of Urtica incisa with chili leaf curl virus and tomato leaf curl betasatellite in Oman - Muhammad Shafiq Shahid; Amir Raza; Muhammad Shafiq; Abdullah M. Al-Sadi; Rob W. Briddon (Journal of Plant Pathology, 2019)

IL-22 in hepatocyte’s survival of Pakistani patients with end stage liver disease: an insight into IL 22 mediated hepato-regenerative pathway - Muhammad Saalim; Saleha Resham; Sobia Manzoor; Hassam Ahmad; Tariq Ali Bangash; Amir Latif; Shahla Jaleel (Molecular Biology Reports, 2019)

Flood hazards: household vulnerability and resilience in disaster-prone districts of Khyber Pakhtunkhwa province, Pakistan - Ashfaq Ahmad Shah; Jingzhong Ye; Muhammad Abid; Jahangir Khan; Syed Muhammad Amir (Natural Hazards, 2018)

CFD simulation of copper(II) extraction with TFA in non-dispersive hollow fiber membrane contactors - Amir Muhammad; Mohammad Younas; Mashallah Rezakazemi (Environmental Science and Pollution Research, 2018)

Biodegradation of plastics: current scenario and future prospects for environmental safety - Temoor Ahmed; Muhammad Shahid; Farrukh Azeem; Ijaz Rasul; Asad Ali Shah; Muhammad Noman; Amir Hameed; Natasha Manzoor; Irfan Manzoor; Sher Muhammad (Environmental Science and Pollution Research, 2018)

Chilling tolerance in three tomato transgenic lines overexpressing CBF3 gene controlled by a stress inducible promoter - Sabir Hussain Shah; Shaukat Ali; Abdul Ahad Qureshi; Muhammad Amir Zia; Jalal-ud -Din; Ghulam Muhammad Ali (Environmental Science and Pollution Research, 2017)

Natural products from Cuscuta reflexa Roxb . with antiproliferation activities in HCT116 colorectal cell lines - Muhammad Riaz; Aishah Bilal; Muhammad Shaiq Ali; Itrat Fatima; Amir Faisal; Muhammad Azhar Sherkheli; Adnan Asghar (Natural Product Research, 2017)

Influence of Metal-Resistant Rhizobacteria on the Growth of Helianthus annuus L. in Cr(VI)-Contaminated Soil - Ali Bahadur; Aftab Afzal; Rizwan Ahmad; Fahad Nasir; Aman Khan; Vishandas Suthar; Gul Jan; Asfa Batool; Muhammad Amir Zia; Muhammad Mahmood-ul-Hassan (Water, Air, & Soil Pollution, 2016)

Distribution of Natural Uranium in Surface and Groundwater Resources: A Review - Amir Waseem; Hussain Ullah; Muhammad Khawar Rauf; Ijaz Ahmad (Critical Reviews in Environmental Science and Technology, 2015)

Estimated daily intake and health risk of heavy metals by consumption of milk - Amir Ismail; Muhammad Riaz; Saeed Akhtar; Tariq Ismail; Zulfiqar Ahmad; Muhammad Saad Hashmi (Food Additives & Contaminants Part B-Surveillance, 2015)

First evidence of the analgesic activity of govaniadine, an alkaloid isolated from Corydalis govaniana Wall. - Naveed Muhammad; Ram Lal Shrestha; Achyut Adhikari; Abdul Wadood; Haroon Khan; Amir Zada Khan; Francesco Maione; Nicola Mascolo; Vincenzo De Feo (Natural Product Research, 2015)

Permian ultrafelsic A-type granite from Besar Islands group, Johor, peninsular Malaysia - Azman A Ghani; Fatin Izzani Hazad; Azmiah Jamil; Quek Long Xiang; Wan Nur Atiqah Wan Ismail; Sun-Lin Chung; Yu-Ming Lai; Muhammad Hatta Roselee; Nur Islami; Kyaw Kyaw Nyein; Meor Hakif Amir Hassan; Mohd Farid Abu Bakar; et al. (Journal of Earth System Science, 2014)

Heavy metals in vegetables and respective soils irrigated by canal, municipal waste and tube well waters - Amir Ismail; Muhammad Riaz; Saeed Akhtar; Tariq Ismail; Mamoona Amir; Muhammad Zafar-ul-Hye (Food Additives & Contaminants Part B-Surveillance, 2014)

Identification of recurrent c.742G>T nonsense mutation in ECM1 in Pakistani families suffering from lipoid proteinosis - Muhammad Nasir; Simeen Ber Rahman; Christian M. K. Sieber; Asif Mir; Amir Latif; Nafees Ahmad; Salman Akbar Malik; Abdul Hameed (Molecular Biology Reports, 2014)

Molecular insights to explore abietane diterpenes as new LOX inhibitors - Inamullah Khan; Muhammad Nisar; Armando Zarrelli; Giovanni Di Fabio; Farah Gul; Syed Naeemuddin Gilani; Muhammad Raza Shah; Amir Zada Khan; Samiullah; Hazrat Amin (Medicinal Chemistry Research, 2013)

Characterization of Afp1, an antifreeze protein from the psychrophilic yeast Glaciozyma antarctica PI12 - Noor Haza Fazlin Hashim; Izwan Bharudin; Douglas Law Sie Nguong; Sakura Higa; Farah Diba Abu Bakar; Sheila Nathan; Amir Rabu; Hidehisa Kawahara; Rosli Md. Illias; Nazalan Najimudin; Nor Muhammad Mahadi; Abdul Munir Abdul Murad (Extremophiles, 2013)

Molecular simulations of bergenin as a new urease inhibitor - Mohammad Arfan; Hazrat Amin; Inamullah Khan; Muhammad Raza Shah; Hamidullah Shah; Amir Zada Khan; Syed Muhammad Ashhad Halimi; Nematullah Khan; Waqar Ahmad Kaleem; Mughal Qayum; Adnan Shahidullah; Muhammad Azam Khan (Medicinal Chemistry Research, 2012)

A mutant l-asparaginase II signal peptide improves the secretion of recombinant cyclodextrin glucanotransferase and the viability of Escherichia coli - Noor Faizah Ismail; Salehhuddin Hamdan; Nor Muhammad Mahadi; Abdul Munir Abdul Murad; Amir Rabu; Farah Diba Abu Bakar; Peter Klappa; Rosli Md. Illias (Biotechnology Letters, 2011)

Synthesis of Novel Fluorescent Cyclohexenone Derivatives and their Partitioning Study in Ionic Micellar Media - Amir Badshah; Saleem Nawaz; Muhammad Faizan Nazar; Syed Sakhawat Shah; Aurangzeb Hasan (Journal of Fluorescence, 2010)

Quantitative estimation of dust fall and smoke particles in Quetta Valley - Muhammad Sami; Amir Waseem; Sher Akbar (Journal of Zhejiang University-SCIENCE B, 2006)